Electrophotographic member, process cartridge and electrophotographic image forming apparatus

The electrophotographic member with a crosslinked urethane and acrylic resin structure stabilizes conductivity and prevents toner charge loss, ensuring high image quality and durability in high-temperature and high-humidity environments.

JP7621773B2Active Publication Date: 2025-01-27CANON KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020189810
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-23
Filing Date
2020-11-13
Publication Date
2025-01-27
Estimated Expiration
2040-11-13

AI Technical Summary

Technical Problem

Conductive rollers used in electronic photo devices experience image failure and reduced toner charge in high-temperature and high-humidity environments, leading to issues in high-speed and high-durability electronic photo processes.

Method used

An electrophotographic member with a single-layer elastic layer composed of a crosslinked urethane resin and a crosslinked acrylic resin, forming an interpenetrating polymer network structure near the surface to stabilize conductivity and suppress charge transfer from toner particles.

Benefits of technology

Maintains high image quality and durability in high-speed electronic photo processes by preventing toner charge loss in harsh environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621773000052
    Figure 0007621773000052
  • Figure 0007621773000053
    Figure 0007621773000053
  • Figure 0007621773000054
    Figure 0007621773000054
Patent Text Reader

Abstract

To provide a member for electrophotography that can maintain high image quality and high durability even in a high-speed electrophotographic process.SOLUTION: A member for electrophotography has a conductive substrate and a single-layer elastic layer as a surface layer. The elastic layer includes a first resin, a second resin, and anions. The first resin is a cross-linked urethane resin. The cross-linked urethane resin is a resin having a specific cationic structure in a molecule. The second resin is at least one of a cross-linked acrylic resin having an ether bond and a cross-linked epoxy resin having an ether bond. In a first area from an outer surface of the elastic layer to a depth of 0.1 μm, the first resin and the second resin form an interpenetrating polymer network structure.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrophotographic member. The present disclosure also relates to a process cartridge and an electrophotographic image forming apparatus having the electrophotographic member. [Background technology]

[0002] In an electrophotographic image forming apparatus (also called "electrophotographic apparatus") according to one embodiment, an image carrier is charged by a charging means, and an electrostatic latent image is formed by a laser. Next, the toner in the developer container is applied onto the developing member by a toner supply roller and a toner regulating member, and development is performed by the toner when the image carrier and the developing member are in contact with each other or in close proximity. Thereafter, the toner on the image carrier is transferred to a recording paper by a transfer means and fixed by heat and pressure, and the toner remaining on the image carrier is removed by a cleaning blade.

[0003] In electrophotographic devices, electroconductive layers are used for developing rollers and charging rollers. The electroconductive layers have an electrical resistance of 10 5 ~10 9 The conductivity must be controlled to about Ω, and the conductivity must be uniform throughout the entire member and stable over time. Conductive agents used to impart a desired conductivity to such a conductive layer include conductive particles such as carbon black and ionic compounds such as quaternary ammonium salts. Ionic compounds and carbon black each exhibit different electrical properties, and it is possible to use both in the conductive layer of an electrophotographic member. Patent Document 1 describes that fogging in a low humidity environment is suppressed by using a conductive roll having a surface layer containing a resin having a urethane bond obtained by reacting an ionic liquid having a cationic structure with a hydroxyl group with an isocyanate. Patent Document 2 describes a conductive roller having improved resistance stability during continuous current flow by incorporating a quaternary ammonium salt group into the main chain. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-202722 A [Patent Document 2] JP 2011-53658 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, electrophotographic devices are required to maintain high image quality and high durability even in faster electrophotographic processes. According to the study by the present inventors, the conductive rollers according to Patent Documents 1 and 2 sometimes caused image defects in long-term durability tests in high-speed processes. For example, when a large number of sheets were printed in a high-temperature and high-humidity environment such as a temperature of 32° C. and a relative humidity of 95%, fogging occurred in the electrophotographic images.

[0006] One aspect of the present disclosure is directed to providing an electrophotographic member capable of maintaining high image quality and high durability even in a high-speed electrophotographic process. Another aspect of the present disclosure is directed to providing a process cartridge that contributes to the stable formation of high-quality electrophotographic images. Yet another aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. [Means for solving the problem]

[0007] According to one aspect of the present disclosure, there is provided an electrophotographic member having a conductive substrate and a single-layer elastic layer as a surface layer, the elastic layer containing a first resin, a second resin, and an anion, the first resin being a crosslinked urethane resin, the crosslinked urethane resin having at least one cationic structure selected from the following structural formulas (1) to (6) in its molecule, the second resin being at least one of a crosslinked acrylic resin having an ether bond (-COC-) and a crosslinked epoxy resin having an ether bond (-COC-), and the first resin and the second resin forming an interpenetrating polymer network structure in a first region from the outer surface of the elastic layer to a depth of 0.1 μm.

[0008] [ka]

[0009] [In structural formula (1), R1 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z1 to Z3 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102) or a monovalent hydrocarbon group having 1 to 4 carbon atoms, with the proviso that at least one of Z1 to Z3 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102)];

[0010] [ka]

[0011] [In structural formula (2), R2 and R3 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing heteroaromatic 5-membered ring together with the nitrogen atom to which they are bonded. Z4 and Z5 each independently represent any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z6 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d1 represents an integer of 0 or 1. However, at least one of Z4 to Z6 is any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).]

[0012] [ka]

[0013] [In structural formula (3), R4 and R5 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing 6-membered heteroaromatic ring together with the nitrogen atom to which it is bonded. Z7 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z8 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d2 represents an integer of 0 to 2, and when d2 is 2, each Z8 may be the same or different. However, at least one of Z7 and Z8 is any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102).]

[0014] [ka]

[0015] [In structural formula (4), R6 and R7 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing heteroalicyclic group together with the nitrogen atom to which they are bonded. Z9 to Z11 each independently represent a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z12 represents a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d3 represents an integer of 0 to 2, and when d3 is 2, each Z12 may be the same or different. However, at least one of Z9 to Z12 is a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102).]

[0016] [ka]

[0017] [In structural formula (5), R8 represents a divalent hydrocarbon group necessary for forming a nitrogen-containing aromatic ring together with the nitrogen atom to which it is bonded. Z13 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z14 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d4 represents an integer of 0 or 1. However, at least one of Z13 and Z14 is any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102).]

[0018] [ka]

[0019] [In structural formula (6), R9 represents a divalent hydrocarbon group necessary to form a nitrogen-containing alicyclic group together with the nitrogen atom to which it is bonded. Z15 and Z16 each independently represent any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z17 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d5 represents an integer of 0 or 1, with the proviso that at least one of Z15 to Z17 is any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102).]

[0020] [ka]

[0021] [In structural formulae (Z101) and (Z102), R10 and R11 each independently represent a divalent hydrocarbon group having a straight chain or a branched chain. The symbol "*" represents a bond to the nitrogen atom in structural formula (1) or a bond to a nitrogen atom in a nitrogen-containing heterocycle or a bond to a carbon atom in a nitrogen-containing heterocycle in structural formulae (2) to (6), and the symbol "**" represents a bond to a carbon atom in the polymer chain constituting the resin having the cationic structure.]

[0022] According to another aspect of the present disclosure, there is provided an electrophotographic member having a conductive substrate and a single-layer elastic layer as a surface layer, the elastic layer comprising a first resin, a second resin, and an anion, the first resin being a crosslinked urethane resin, the crosslinked urethane resin being a resin having in its molecule at least one cationic structure selected from the above structural formulas (1) to (6), the second resin being at least one of a crosslinked acrylic resin having an ether bond and a crosslinked epoxy resin having an ether bond, a first region from the outer surface of the elastic layer to a depth of 0.1 μm comprising the first resin and the second resin, wherein A1 (° C.) is a peak top temperature of a thermal chromatogram derived from the second resin measured from a first sample sampled from the first region, and A2 (° C.) is a peak top temperature of a thermal chromatogram derived from the second resin measured from a second sample obtained by decomposing the first resin contained in the first sample, and A1 and A2 are expressed by the following formula (1): Formula (1) A1>A2 There is provided an electrophotographic member which satisfies the relationship given by:

[0023] According to another aspect of the present disclosure, there is provided an electrophotographic process cartridge configured to be detachably mountable to a main body of an electrophotographic apparatus, the process cartridge including the electrophotographic member described above. Furthermore, according to another aspect of the present disclosure, there is provided an image forming apparatus having an image carrier for carrying an electrostatic latent image, a charging device for primarily charging the image carrier, an exposure device for forming an electrostatic latent image on the primarily charged image carrier, a developing member for developing the electrostatic latent image with toner to form a toner image, and a transfer device for transferring the toner image to a transfer material, wherein the developing member is the electrophotographic member described above. Effect of the Invention

[0024] According to one aspect of the present disclosure, it is possible to obtain an electrophotographic member capable of maintaining high image quality and high durability even in a high-speed electrophotographic process. According to another aspect of the present disclosure, it is possible to obtain a process cartridge that contributes to the stable formation of a high-quality electrophotographic image. Furthermore, according to another aspect of the present disclosure, it is possible to obtain an electrophotographic image forming apparatus capable of stably forming a high-quality electrophotographic image. [Brief description of the drawings]

[0025] [Figure 1A] FIG. 2 is a conceptual diagram illustrating an example of a developing member according to the present disclosure. [Figure 1B] FIG. 2 is a conceptual diagram illustrating an example of a developing member according to the present disclosure. [Diagram 2] FIG. 1 is a schematic diagram (schematic cross-sectional view) of a method for irradiating a conductive substrate with excimer UV light according to the present disclosure. [Diagram 3] 1 is a schematic configuration diagram illustrating an example of an electrophotographic image forming apparatus according to the present disclosure. [Figure 4] FIG. 2 is a schematic configuration diagram illustrating an example of a process cartridge according to the present disclosure. [Diagram 5] 2 is a schematic diagram illustrating an example of a cross section of a developing member according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present inventors have found that when the conductive rollers according to Patent Documents 1 and 2 are used as developing rollers, when a large number of sheets are printed in a high-temperature and high-humidity environment, a problem occurs in that fogging occurs on the electrophotographic image, and have investigated the mechanism. In the process, they have found that the charge amount of the toner carried on the surface of the conductive roller in the electrophotographic image forming process is reduced compared to the initial state. The present inventors have then hypothesized that the cause of the reduction in the charge amount of the toner is as follows.

[0027] In the process of forming a large number of electrophotographic images, anions in the surface layer of the conductive roller are unevenly distributed on the side of the surface layer that is closer to the substrate. The concentration of the counter ions, the anions, decreases, causing a relative increase in the concentration of free cations on the outer surface of the conductive roller. The molecular mobility of free cations near the surface increases in a high-temperature, high-humidity environment. It is presumed that this makes it easier for the charge of the toner particles in direct contact with the outer surface of the conductive roller to transfer to the conductive roller, causing a decrease in the charge of the toner.

[0028] Therefore, the present inventors have conducted research to obtain an electrophotographic member capable of suppressing the transfer of charge from the toner particles to the conductive roller. As a result, it was found that, by using an electrophotographic member having a surface layer having a specific structure, the transfer of charge from the toner particles can be more reliably suppressed even in a high-temperature and high-humidity environment.

[0029] An electrophotographic member according to an embodiment of the present disclosure has a conductive substrate and a single elastic layer as a surface layer. The elastic layer includes a first resin, a second resin, and an anion. The first resin is a crosslinked urethane resin having a specific cationic structure in the molecule. The second resin is at least one of a crosslinked acrylic resin having an ether bond and a crosslinked epoxy resin having an ether bond. In a first region from the outer surface of the elastic layer to a depth of 0.1 μm, the first resin and the second resin form an interpenetrating polymer network structure.

[0030] The present inventors speculate as follows about the reason why such an electrophotographic member can suppress the occurrence of fog even during durable use involving printing a large number of sheets under a high-temperature and high-humidity environment.

[0031] The specific cationic structure includes a urethane bond formed by the reaction of a hydroxyl group with an isocyanate group, or a urea bond formed by the reaction of an amino group with an isocyanate group. The urethane bonds, the urea bonds, and the urethane and urea bonds interact with each other to form hard segments. As a result, the mobility of the polymer chain of the crosslinked urethane resin (first resin) having the cationic structure is suppressed. In addition, the second resin forms an interpenetrating polymer network structure with the first resin in the first region from the outer surface of the elastic layer to a depth of 0.1 μm. Furthermore, the ether bond of the second resin interacts with the urethane bond or the urea bond, thereby suppressing the mobility of the hard segment itself. As a result, the molecular mobility of the polymer chain of the crosslinked urethane resin is more reliably suppressed even in a high-temperature, high-humidity environment. As a result, it is considered that the transfer of charge from the toner particles can be more reliably suppressed even in a high-temperature, high-humidity environment.

[0032] <Interpenetrating polymer network structure> An interpenetrating polymer network (IPN) is a structure in which two or more polymeric networks are intertwined and entangled without being bound by covalent bonds. This structure cannot be unraveled unless the molecular chains that form the network are cut. There are several methods for forming an IPN structure. For example, there is a sequential network formation method in which a network of the first component polymer is formed first, then swelled with the second component monomer and polymerization initiator, and then a network of the second component polymer is formed. Alternatively, there is a simultaneous network formation method in which a first component monomer and a second component monomer, each of which has a different reaction mechanism, and a polymerization initiator for each are mixed and simultaneously formed into a network.

[0033] In this embodiment, a cross-linked urethane resin and a cross-linked acrylic resin having an ether bond or an epoxy resin having an ether bond form an IPN structure. This IPN structure is formed by impregnating a cross-linked urethane resin as a first resin with an acrylic monomer or a glycidyl ether monomer and a polymerization initiator from the outer surface of the conductive roller, and then polymerizing the acrylic monomer or the glycidyl ether monomer to form a second resin. As a result, the acrylic monomer or the glycidyl ether monomer penetrates into the three-dimensional network structure of the cross-linked urethane resin and polymerizes to form an IPN structure. Furthermore, the ether bond of the second resin also interacts with the urethane bond or urea bond contained in the crosslinked urethane resin, so that the molecular mobility of the hard segment formed by the interaction of the urethane bond or urea bond is more reliably suppressed.

[0034] In this embodiment, the molecular mobility of the urethane bond or urea bond of the crosslinked urethane resin is suppressed, and since the cationic structure is also bonded to the crosslinked urethane resin through a urethane bond or urea bond, the molecular mobility of the cationic structure is also suppressed, thereby preventing the charge of the toner particles from transferring to the conductive roller even after printing a large number of sheets under a high temperature and high humidity environment.

[0035] Hereinafter, the electrophotographic member according to the present disclosure will be described using a roller-shaped developing member (developing roller), but the shape of the electrophotographic member is not limited thereto. FIG. 1A is a sectional view in the circumferential direction of a roller-shaped electrophotographic member having a conductive mandrel 2 as a conductive substrate and a surface layer 1 on the peripheral surface of the substrate. 1B is a circumferential cross-sectional view of a roller-shaped electrophotographic member having a mandrel 2 as a conductive base and an intermediate layer 3 between the surface layer 1 and the mandrel 2. The intermediate layer 3 is not limited to a single layer, and may be a multi-layer. For example, in a non-magnetic one-component contact development process, an electrophotographic member having a surface layer 1 provided on a conductive base having an intermediate layer 3 laminated on the mandrel 2 is preferably used.

[0036] [Conductive substrate] The conductive substrate may be a cylindrical or hollow cylindrical conductive mandrel, or such a mandrel with one or more conductive intermediate layers provided thereon. The mandrel is cylindrical or hollow cylindrical in shape and is made of the following conductive materials: metals or alloys such as aluminum, copper alloys, and stainless steel; iron plated with chromium or nickel; and conductive synthetic resins. A known adhesive may be applied to the surface of the mandrel 2 to improve adhesion to the outer peripheral intermediate layer 3 and surface layer 1.

[0037] [Middle layer] As described above, in the non-magnetic one-component contact development process, an electrophotographic member having an intermediate layer 3 laminated between the mandrel 2 and the surface layer 1 is preferably used. The intermediate layer imparts hardness and elasticity to the developing member so that the developing member can be pressed against the image carrier with an appropriate nip width and nip pressure so that the toner can be supplied to the electrostatic latent image formed on the surface of the image carrier without excess or deficiency. The intermediate layer is preferably formed by a molding of a normal rubber material. Examples of rubber materials include the following: ethylene-propylene-diene copolymer rubber (EPDM), acrylonitrile-butadiene rubber (NBR), chloroprene rubber (CR), natural rubber (NR), isoprene rubber (IR), styrene-butadiene rubber (SBR), fluororubber, silicone rubber, epichlorohydrin rubber, NBR hydride, and urethane rubber. These may be used alone or in combination of two or more. Among these, silicone rubber is particularly preferred because it is less likely to cause compression set even when in contact with other members (such as a toner regulating member) for a long period of time. Specific examples of silicone rubber include cured products of addition-curing silicone rubber. The intermediate layer may be an intermediate layer obtained by compounding the above-mentioned rubber material with a conductivity imparting agent such as an electronic conductive material or an ionic conductive material. The volume resistivity of the intermediate layer is preferably 10 3 Ωcm or more 10 11 Ωcm or less, more preferably 10 4 Ωcm or more 10 10The resistance is adjusted to Ωcm or less.

[0038] Examples of electronically conductive substances include the following: carbon black such as conductive carbon, carbon for rubber, and carbon for color (ink); conductive carbon black such as Ketjen Black EC and acetylene black; carbon for rubber such as SAF, ISAF, HAF, FEF, GPF, SRF, FT, and MT; carbon for color (ink) that has been subjected to oxidation treatment; metals and metal oxides thereof such as copper, silver, and germanium. Among these, conductive carbon [conductive carbon, carbon for rubber, and carbon for color (ink)] is preferred because it is easy to control conductivity with a small amount. Examples of the ionically conductive substance include the following: inorganic ionically conductive substances such as sodium perchlorate, lithium perchlorate, calcium perchlorate, and lithium chloride; and organic ionically conductive substances such as modified aliphatic dimethylammonium ethosulfate and stearyl ammonium acetate. These conductivity imparting agents are used in an amount necessary to adjust the intermediate layer to an appropriate volume resistivity as described above, and are usually used in an amount within the range of 0.5 parts by mass to 50 parts by mass per 100 parts by mass of the binder resin.

[0039] In addition, the intermediate layer may further contain various additives such as plasticizers, fillers, extenders, vulcanizing agents, vulcanization aids, crosslinking aids, curing inhibitors, antioxidants, antiaging agents, and processing aids, as necessary. Examples of fillers include silica, quartz powder, and calcium carbonate. These optional components are blended in amounts that do not inhibit the function of the intermediate layer. The intermediate layer has the elasticity required for a developing member, and preferably has an Asker C hardness of 20 degrees or more and 100 degrees or less, and a thickness of 0.3 mm or more and 6.0 mm or less. The materials for the intermediate layer can be mixed using a dynamic mixer such as a single-screw continuous kneader, a twin-screw continuous kneader, a twin roll, a kneader mixer, or a trimix, or a static mixer such as a static mixer.

[0040] The method of forming the intermediate layer on the mandrel is not particularly limited, and examples thereof include a molding method, an extrusion molding method, an injection molding method, and a coating molding method. In the molding method, for example, first, a piece for holding the mandrel in the mold is fixed to both ends of a cylindrical mold, and an injection port is formed in the piece. Next, the mandrel is placed in the mold, and the material for the intermediate layer is injected from the injection port, and the mold is heated at a temperature at which the material hardens, and then demolded. In the extrusion molding method, for example, a method of extruding the mandrel and the material for the intermediate layer together using a crosshead extruder, hardening the material, and forming the intermediate layer around the mandrel can be mentioned. The surface of the intermediate layer can be modified by a surface modification method such as surface polishing, corona treatment, frame treatment, or excimer treatment in order to improve adhesion to the surface layer.

[0041] [Surface layer] The surface layer constituting the outer surface of the electrophotographic member that serves as the toner carrying surface is formed of a single elastic layer, and in the case of a roller-shaped member, is provided on the outermost peripheral surface. The surface layer can be formed directly on the mandrel, but the surface layer can also be formed on the outer peripheral surface of a mandrel having an intermediate layer provided thereon as a base. The surface layer contains a first resin, which is a crosslinked urethane resin, a second resin, which is at least one of a crosslinked acrylic resin having an ether bond and a crosslinked epoxy resin having an ether bond, and an anion. In the surface region (first region) from the outer surface to a depth of 0.1 μm, the crosslinked urethane resin and the crosslinked acrylic resin or the crosslinked epoxy resin form an IPN structure. The surface layer may contain resin particles for forming convex portions on the outer surface of the electrophotographic member. The surface layer may also contain fine particles to roughen the outer surface. Specifically, fine particles of polyurethane resin, polyester resin, polyether resin, polyamide resin, acrylic resin, and polycarbonate resin can be used. These are also preferably crosslinked resin particles. When an IPN structure is formed on the outer surface side of the surface layer, an IPN structure may also be formed inside the crosslinked resin particles. The volume average particle diameter of the fine particles is preferably 1.0 μm or more and 30 μm or less, and the surface roughness (ten-point average roughness) Rzjis formed by the fine particles is preferably 0.1 μm or more and 20 μm or less. Rzjis is a value measured based on JIS B0601 (1994).

[0042] [Method of forming surface layer] The method of forming the surface layer having an IPN structure formed from a cross-linked acrylic resin or a cross-linked epoxy resin will be described below. The surface layer of this embodiment can be formed by the following steps (i) to (iii). (i) forming a resin layer containing a cross-linked urethane resin as a first resin on a conductive substrate; (ii) impregnating the outer surface of the resin layer with a liquid acrylic monomer or a liquid glycidyl ether monomer; and (iii) A step of curing the impregnated acrylic monomer or glycidyl ether monomer.

[0043] Before the step of forming a resin layer containing a cross-linked urethane resin as the first resin on the conductive substrate, the conductive substrate may be surface-treated. Fig. 2 shows a schematic diagram (schematic cross-sectional view) of a method of irradiating an conductive substrate 44 having an intermediate layer 3 according to the present disclosure with excimer UV. As shown in Fig. 2, four conductive substrates 44 are arranged on a concentric circle of an excimer UV lamp 12 attached to a water-cooled heat sink built-in holder 11, and the conductive substrates 44 are rotated while being irradiated with excimer light from the excimer UV lamp 12, whereby the surface treatment of the intermediate layer 3 is performed. The resin layer containing the crosslinked urethane resin is preferably formed by a coating molding method using a liquid paint, although there is no particular limitation. For example, the resin layer can be formed by dispersing and mixing each material for the resin layer in a solvent to form a paint, applying the paint on a conductive substrate, and drying and solidifying or heating and curing the paint. As the solvent, a polar solvent is preferable from the viewpoint of compatibility with polyols and isocyanate compounds, which are raw materials for the crosslinked urethane resin. Examples of the polar solvent include alcohols such as methanol, ethanol, and n-propanol, ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, and esters such as methyl acetate and ethyl acetate. Among these, one or more solvents having good compatibility with other materials can be mixed and used. The solid content when forming the paint can be freely adjusted by the amount of the solvent mixed. For dispersion and mixing, a known dispersing device using beads such as a sand mill, a paint shaker, a dyno mill, and a pearl mill can be used. As the coating method, dip coating, ring coating, spray coating, or roll coating can be used.

[0044] The drying and solidifying or heat curing is not particularly limited as long as the crosslinking of the urethane resin proceeds, but a temperature of 50° C. or higher is preferable, and a temperature of 70° C. or higher is more preferable. Next, the resin layer formed as described above is impregnated with a liquid acrylic monomer or a glycidyl ether monomer. The liquid acrylic monomer or the glycidyl ether monomer can be impregnated as it is or as an impregnation treatment liquid appropriately diluted with various solvents. By appropriately diluting the liquid acrylic monomer or the glycidyl ether monomer with various solvents, a surface layer with a more uniform surface composition can be obtained. The solvent can be freely selected as long as it satisfies both the affinity with the resin layer and the solubility of the acrylic monomer or the glycidyl ether monomer. For example, alcohols such as methanol, ethanol, and n-propanol, ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, and esters such as methyl acetate and ethyl acetate can be included. In addition, a polymerization initiator can be appropriately mixed into the impregnation treatment liquid. Details of the polymerization initiator will be described later. The method of impregnation with the impregnation treatment liquid is not particularly limited, but dip coating, ring coating, spray coating, or roll coating can be used.

[0045] After the impregnation treatment with the impregnation treatment solution, the acrylic monomer or the glycidyl ether monomer is polymerized and cured to form a surface layer. The polymerization and curing method is not particularly limited, and any known method can be used. Specifically, methods such as heat curing and ultraviolet irradiation can be used. By such a process, the cross-linked acrylic resin or cross-linked epoxy resin is introduced into the network structure of the cross-linked urethane resin of the resin layer in a mutually intertwined manner, and an IPN structure can be formed. This IPN structure is formed by impregnating the cross-linked urethane resin as the first resin with an acrylic monomer or a glycidyl ether monomer and a polymerization initiator from the outer surface of the developing member, and then forming a cross-linked acrylic resin or a cross-linked epoxy resin as the second resin. In this case, the acrylic monomer or the glycidyl ether monomer penetrates into the three-dimensional network structure of the cross-linked urethane resin and polymerizes to form a network structure of the cross-linked acrylic resin or the cross-linked epoxy resin.

[0046] From the viewpoint of film strength and flexibility, the thickness of the surface layer thus obtained is preferably 2.0 μm or more and 150.0 μm or less. Note that the thickness of the surface layer here refers to the thickness of the part excluding the parts protruding in a convex shape due to the addition of coarse particles, etc.

[0047] [Cross-linked urethane resin] Crosslinked urethane resins are suitable as binders because of their excellent flexibility and strength. The urethane resins can be obtained from polyols and isocyanates, and optionally from chain extenders. Polyols include polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, acrylic polyols, and mixtures thereof. Examples of isocyanates include the following: Tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate (NDI), tolidine diisocyanate (TODI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), phenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), cyclohexane diisocyanate, and mixtures thereof. Chain extenders include difunctional low molecular weight diols such as ethylene glycol, 1,4-butanediol, 3-methylpentanediol, trifunctional low molecular weight triols such as trimethylolpropane, and mixtures thereof. In addition, a prepolymer type isocyanate compound having an isocyanate group at a terminal, which is obtained by reacting the above-mentioned various isocyanate compounds with various polyols in advance in a state where the isocyanate group is in excess, may be used. In addition, as these isocyanate compounds, materials in which the isocyanate group is blocked with various blocking agents such as MEK oxime may be used. Regardless of which material is used, a urethane resin can be obtained by reacting the polyol with the isocyanate by heating. Furthermore, if either or both of the polyol and isocyanate have a branched structure and three or more functional groups, the resulting urethane resin will be a crosslinked urethane resin. The crosslinked urethane resin according to the present disclosure has at least one cationic structure selected from the structural formulas (1) to (6) in the molecule. The crosslinked urethane resin having a cationic structure can be obtained, for example, by reacting an ionic compound having at least one functional group derived from a hydroxyl group or an amino group with a binder resin. The binder resin is preferably a binder resin obtained by reacting a compound other than the ionic compound, preferably a polyol with a polyisocyanate. The ionic compound is a precursor of at least one cationic structure selected from the group consisting of structures represented by structural formulas (1) to (6). The structures represented by structural formulas (1) to (6) are described below.

[0048] [ka]

[0049] In structural formula (1), R1 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The hydrocarbon group is preferably an alkyl group. Z1 to Z3 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102) or a monovalent hydrocarbon group having 1 to 4 carbon atoms. However, at least one of Z1 to Z3 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102). The monovalent hydrocarbon group is preferably an alkyl group. The structure represented by structural formula (1) is, for example, a structure derived from an ionic compound having an ammonium cation having at least one of a hydroxyl group or an amino group. That is, the ionic compound has at least one hydroxyl group, and by reacting the hydroxyl group with an isocyanate group, a crosslinked urethane resin having at least one structure represented by structural formula (Z101) is obtained. In addition, when the ionic compound has at least one amino group, by reacting the amino group with an isocyanate group, a crosslinked urethane resin having at least one structure represented by structural formula (Z102) is obtained.

[0050] An example of a cation of an ionic compound capable of forming the structure represented by structural formula (1) is an ammonium cation having a hydroxyl group. 2-hydroxyethyltrimethylammonium cation, 2-hydroxyethyltriethylammonium cation, 4-hydroxybutyltrimethylammonium cation, 4-hydroxybutyl-tri-n-butylammonium cation, 8-hydroxyoctyltrimethylammonium cation, 8-hydroxyoctyl-tri-n-butylammonium cation; bis(hydroxymethyl)dimethylammonium cation, bis(2-hydroxyethyl)dimethylammonium cation, bis(3-hydroxypropyl)dimethylammonium cation, bis(4-hydroxybutyl)dimethylammonium cation, bis(8-hydroxyoctyl)dimethylammonium cation, bis(8-hydroxyoctyl)-di-n-butylammonium cation; Tris(hydroxymethyl)methylammonium cation, tris(2-hydroxyethyl)methylammonium cation, tris(3-hydroxypropyl)methylammonium cation, tris(4-hydroxybutyl)methylammonium cation, tris(8-hydroxyoctyl)methylammonium cation; and derivatives thereof. Examples of ammonium cations having amino groups include cations having a structure in which some or all of the hydroxyl groups of the above-mentioned cations are substituted with amino groups.

[0051] [ka]

[0052] In structural formula (2), R2 and R3 each represent a divalent hydrocarbon group necessary to form a nitrogen-containing heteroaromatic five-membered ring together with the nitrogen atom to which it is bonded. In order to form an aromatic five-membered ring together with the two nitrogen atoms, one of R2 and R3 is a hydrocarbon group having one carbon atom, and the other is a hydrocarbon group having two carbon atoms. The nitrogen-containing heteroaromatic 5-membered ring of structural formula (2) may have a substituent Z6 other than a hydrogen atom. Z6 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. d1 represents an integer of 0 or 1. Z4 and Z5 each independently represent a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. At least one of Z4 to Z6 is a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102). The structure represented by structural formula (2) is, for example, a structure derived from an ionic compound having at least one hydroxyl group or amino group and a nitrogen-containing heteroaromatic five-membered ring cation containing two nitrogen atoms. That is, when the ionic compound has at least one hydroxyl group, a urethane resin having at least one structure represented by structural formula (Z101) is obtained by reacting the hydroxyl group with an isocyanate group. When the ionic compound has at least one amino group, a crosslinked urethane resin having at least one structure represented by structural formula (Z102) is obtained by reacting the amino group with an isocyanate group. A specific example of the structural formula (2) is the structure shown in the following structural formula (2)-1.

[0053] [ka]

[0054] In the structural formula (2)-1, Z4 to Z6 and d1 are defined the same as Z4 to Z6 and d1 in the structural formula (2).

[0055] Examples of cations of ionic compounds capable of forming the structure represented by structural formula (2) include cations having an imidazolium ring structure and a hydroxyl group, as shown below. 1-methyl-3-hydroxymethylimidazolium cation, 1-methyl-3-(2-hydroxyethyl)imidazolium cation, 1-methyl-3-(3-hydroxypropyl)imidazolium cation, 1-methyl-3-(4-hydroxybutyl)imidazolium cation, 1-methyl-3-(6-hydroxyhexyl)imidazolium cation, 1-methyl-3-(8-hydroxyoctyl)imidazolium cation, 1-ethyl-3-(2-hydroxyethyl)imidazolium cation, 1-n-butyl-3-(2-hydroxyethyl)imidazolium cation, 1,3-dimethyl-2-(2-hydroxyethyl)imidazolium cation, 1,3-dimethyl-2-(4-hydroxybutyl)imidazolium cation, 1,3-dimethyl-4-(2-hydroxyethyl)imidazolium cation; 1,3-bishydroxymethylimidazolium cation, 1,3-bis(2-hydroxyethyl)imidazolium cation, 2-methyl-1,3-bishydroxymethylimidazolium cation, 2-methyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 4-methyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 2-ethyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 4-ethyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 2-n-butyl-1,3-bis(2-hydroxyethyl)imidazolium cation , 4-n-butyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 1,3-bis(3-hydroxypropyl)imidazolium cation, 1,3-bis(4-hydroxybutyl)imidazolium cation, 1,3-bis(6-hydroxyhexyl)imidazolium cation, 1,3-bis(8-hydroxyoctyl)imidazolium cation, 1-methyl-2,3-bis(2-hydroxyethyl)imidazolium cation, 1-methyl-3,4-bis(2-hydroxyethyl)imidazolium cation, 1-methyl-3,5-bis(2-hydroxyethyl)imidazolium cation; 1,2,3-trishydroxymethylimidazolium cation, 1,2,3-tris(2-hydroxyethyl)imidazolium cation, 1,2,3-tris(3-hydroxypropyl)imidazolium cation, 1,2,3-tris(4-hydroxybutyl)imidazolium cation, 1,2,3-tris(6-hydroxyhexyl)imidazolium cation, 1,2,3-tris(8-hydroxyoctyl)imidazolium cation, 1,3,4-tris(2-hydroxyethyl)imidazolium cation, 1,3,4-tris(3-hydroxypropyl)imidazolium cation, 1,3,4-tris(4-hydroxybutyl)imidazolium cation, 1,3,4-tris(6-hydroxyhexyl)imidazolium cation, 1,3,4-tris(8-hydroxyoctyl)imidazolium cation; and derivatives thereof. Examples of the cation having an amino group include cations having a structure in which some or all of the hydroxyl groups of the above-mentioned cations are substituted with amino groups.

[0056] [ka]

[0057] In structural formula (3), R4 and R5 each represent a divalent hydrocarbon group necessary to form a nitrogen-containing 6-membered heteroaromatic ring together with the nitrogen atom to which they are attached. In order to form a heteroaromatic 6-membered ring together with the two nitrogen atoms, for example, one of R4 and R5 may be a hydrocarbon group having 1 carbon atom, and the other may be a hydrocarbon group having 3 carbon atoms. Alternatively, both R4 and R5 may be hydrocarbon groups having 2 carbon atoms. The nitrogen-containing heteroaromatic 6-membered ring of structural formula (3) may have Z8 as a substituent other than a hydrogen atom. Z8 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. d2 represents an integer of 0 to 2. When d2 is 2, Z8 may be the same or different. Z7 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. At least one of Z7 and Z8 is any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102). The structure represented by structural formula (3) is, for example, a structure derived from an ionic compound having at least one hydroxyl group or amino group and a nitrogen-containing heteroaromatic 6-membered ring cation containing two nitrogen atoms. That is, when the ionic compound has at least one hydroxyl group, a crosslinked urethane resin having at least one structure represented by structural formula (Z101) is obtained by reacting the hydroxyl group with an isocyanate group. When the ionic compound has at least one amino group, a crosslinked urethane resin having at least one structure represented by structural formula (Z102) is obtained by reacting the amino group with an isocyanate group. Examples of the nitrogen-containing heteroaromatic 6-membered ring in the structural formula (3) include a pyrimidine ring and a pyrazine ring. A specific example of the structural formula (3) is the structure shown in the following structural formula (3)-1.

[0058] [ka]

[0059] In structural formula (3)-1, Z7, Z8 and d2 have the same meanings as those in structural formula (3). Examples of cations of ionic compounds capable of forming the structure represented by structural formula (3) include cations having a pyrimidine ring structure and a hydroxyl group, as shown below. 1,4-bis(2-hydroxyethyl)pyrimidinium cation, 1,5-bis(3-hydroxypropyl)pyrimidinium cation, 1-(4-hydroxybutyl)-4-(2-hydroxyethyl)pyrimidinium cation, 1,4-bis(2-hydroxyethyl)-2-methylpyrimidinium cation; and derivatives thereof. Examples of the cation having at least one amino group include cations having a structure in which some or all of the hydroxyl groups of the above-mentioned cations are substituted with amino groups.

[0060] [ka]

[0061] In structural formula (4), R6 and R7 each represent a divalent hydrocarbon group necessary to form a nitrogen-containing heteroalicyclic group together with the nitrogen atom to which they are bonded. Examples of the nitrogen-containing heteroalicyclic group include a 5- to 7-membered ring structure. Examples of R6 and R7 include an alkylene group having 1 to 3 carbon atoms or an alkenylene group having 2 to 3 carbon atoms, which can form a 5- to 7-membered ring structure. Among these, an alkylene group is preferred. The nitrogen-containing heteroalicyclic group of structural formula (4) may have Z12 as a substituent other than a hydrogen atom. Z12 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. d3 represents an integer of 0 to 2, and when d3 is 2, Z12 may be the same or different. Z9 to Z11 each independently represent a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. Furthermore, at least one of Z9 to Z12 is a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102). The structure represented by structural formula (4) is, for example, a structure derived from an ionic compound having at least one hydroxyl group or amino group and a nitrogen-containing heteroalicyclic cation containing two nitrogen atoms. That is, when the ionic compound has at least one hydroxyl group, a crosslinked urethane resin having at least one structure represented by structural formula (Z101) is obtained by reacting the hydroxyl group with an isocyanate group. When the ionic compound has at least one amino group, a crosslinked urethane resin having at least one structure represented by structural formula (Z102) is obtained by reacting the amino group with an isocyanate group. Examples of the nitrogen-containing heteroalicyclic group in structural formula (4) include a piperazine group (6 members), an imidazoline group (5 members), an imidazolidine group (5 members), a 1,3-diazepane group (7 members), and a 1,4-diazepane group (7 members). A specific example of the structural formula (4) is the structure shown in the following structural formula (4)-1.

[0062] [ka]

[0063] In the structural formula (4)-1, Z9 to Z12 and d3 have the same meanings as those in the structural formula (4). Examples of cations of ionic compounds capable of forming the structure represented by structural formula (4) include cations having a piperazine group and a hydroxyl group, as shown below. 1,1-bis(2-hydroxyethyl)piperazinium cation, 1,1,4-tris(2-hydroxyethyl)piperazinium cation, 1,4-bis(3-hydroxypropyl)-1-ethylpiperazinium cation, 1,4-bis(2-hydroxyethyl)-1,3-diethylpiperazinium cation; and derivatives thereof. Examples of the cation having at least one amino group include cations having a structure in which some or all of the hydroxyl groups of the above-mentioned cations are substituted with amino groups.

[0064] [ka]

[0065] In structural formula (5), R8 represents a divalent hydrocarbon group necessary for forming a nitrogen-containing heteroaromatic ring together with the nitrogen atom to which it is bonded. The nitrogen-containing heteroaromatic ring is a 5- to 7-membered ring, preferably a 5- or 6-membered ring, and more preferably a 6-membered ring. Z13 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. As the monovalent hydrocarbon group, an alkyl group is preferable. The nitrogen-containing heteroaromatic ring may have Z14 as a substituent other than hydrogen. Z14 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. d4 represents an integer of 0 or 1. At least one of Z13 and Z14 is any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102). The structure represented by structural formula (5) is, for example, a structure derived from an ionic compound having at least one of either a hydroxyl group or an amino group and a nitrogen-containing aromatic ring cation containing one nitrogen atom. When the cation of the ionic compound has at least one hydroxyl group, a crosslinked urethane resin having at least one structure represented by structural formula (Z101) is obtained by reacting the hydroxyl group with an isocyanate group. When the cation of the ionic compound has at least one amino group, a crosslinked urethane resin having at least one structure represented by structural formula (Z102) is obtained by reacting the amino group with an isocyanate group. Examples of the nitrogen-containing aromatic ring in the structural formula (5) include a pyrrole ring, a pyridine ring, and an azepine ring. A specific example of the structural formula (5) is the structure shown in the following structural formula (5)-1.

[0066] [ka]

[0067] In structural formula (5)-1, Z13, Z14 and d4 have the same meanings as those in structural formula (5).

[0068] Examples of cations of ionic compounds capable of forming the structure represented by structural formula (5) include cations having a pyridine ring structure and a hydroxyl group, as shown below. 1-hydroxymethylpyridinium cation, 1-(2-hydroxyethyl)pyridinium cation, 1-(3-hydroxypropyl)pyridinium cation, 1-(4-hydroxybutyl)pyridinium cation, 1-(6-hydroxyhexyl)pyridinium cation, 1-(8-hydroxyoctyl)pyridinium cation, 2-methyl-1-(2-hydroxyethyl)pyridinium cation, 3-methyl-1-(2-hydroxyethyl)pyridinium cation, 4-methyl-1-(2-hydroxyethyl)pyridinium cation, 3-ethyl-1-(2-hydroxyethyl)pyridinium cation, 3-n-butyl-1-(2-hydroxy ethyl)pyridinium cation, 1-methyl-2-hydroxymethylpyridinium cation, 1-methyl-3-hydroxymethylpyridinium cation, 1-methyl-4-hydroxymethylpyridinium cation, 1-methyl-2-(2-hydroxyethyl)pyridinium cation, 1-methyl-3-(2-hydroxyethyl)pyridinium cation, 1-methyl-4-(2-hydroxyethyl)pyridinium cation, 1-ethyl-3-(2-hydroxyethyl)pyridinium cation, 1-n-butyl-3-(2-hydroxyethyl)pyridinium cation, 2-methyl-4-n-butyl-1-(2-hydroxyethyl)pyridinium cation; 1,2-bishydroxymethylpyridinium cation, 1,3-bishydroxymethylpyridinium cation, 1,4-bishydroxymethylpyridinium cation, 1,2-bis(2-hydroxyethyl)pyridinium cation, 1,3-bis(2-hydroxyethyl)pyridinium cation, 1,4-bis(2-hydroxyethyl)pyridinium cation, 1,2-bis(3-hydroxypropyl)pyridinium cation, 1,3-bis(3-hydroxypropyl)pyridinium cation, 1,4-bis(3-hydroxypropyl)pyridinium cation, 1,2-bis(4-hydroxybutyl)pyridinium cation, 1,3-bis(4-hydroxybutyl)pyridinium cation, 1,4-bis(4-hydroxybutyl)pyridinium cation lysinium cation, 1,2-bis(6-hydroxyhexyl)pyridinium cation, 1,3-bis(6-hydroxyhexyl)pyridinium cation, 1,4-bis(6-hydroxyhexyl)pyridinium cation, 1,2-bis(8-hydroxyoctyl)pyridinium cation, 1,3-bis(8-hydroxyoctyl)pyridinium cation, 1,4-bis(8-hydroxyoctyl)pyridinium cation, 2-methyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 2-ethyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 5-methyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 5-ethyl-1,3-bis(2-hydroxyethyl)pyridinium cation; 1,2,4-trishydroxymethylpyridinium cation, 1,2,4-tris(2-hydroxyethyl)pyridinium cation, 1,2,4-tris(3-hydroxypropyl)pyridinium cation, 1,2,4-tris(4-hydroxybutyl)pyridinium cation, 1,2,4-tris(6-hydroxyhexyl)pyridinium cation, 1,2,4-tris(8-hydroxyoctyl)pyridinium cation, 1,3,5-trishydroxymethylpyridinium cation, 1,3,5-tris(2-hydroxyethyl)pyridinium cation, 1,3,5-tris(3-hydroxypropyl)pyridinium cation, 1,3,5-tris(4-hydroxybutyl)pyridinium cation, 1,3,5-tris(6-hydroxyhexyl)pyridinium cation, 1,3,5-tris(8-hydroxyoctyl)pyridinium cation; and derivatives thereof. Examples of the cation having at least one amino group include cations having a structure in which some or all of the hydroxyl groups of the above-mentioned cations are substituted with amino groups.

[0069] [ka]

[0070] In structural formula (6), R9 represents a divalent hydrocarbon group necessary for forming a nitrogen-containing alicyclic group together with the nitrogen atom to which it is bonded. Examples of the nitrogen-containing alicyclic group include 5- to 8-membered ring structures. R9 may be an alkylene group having 4 to 7 carbon atoms or an alkenylene group having 4 to 7 carbon atoms, with an alkylene group being preferred. The nitrogen-containing alicyclic group may have Z17 as a substituent other than a hydrogen atom. Z17 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. d5 represents an integer of 0 or 1. Z15 and Z16 each independently represent a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. The monovalent hydrocarbon group is preferably an alkyl group. At least one of Z15 to Z17 is a structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102). The structure represented by structural formula (6) is a structure derived from an ionic compound having at least one hydroxyl group or one amino group and having a nitrogen-containing alicyclic cation containing one nitrogen atom. When the cation of the ionic compound has at least one hydroxyl group, the hydroxyl group is reacted with an isocyanate group to obtain a crosslinked urethane resin having at least one structure represented by structural formula (Z101).When the cation of the ionic compound has at least one amino group, the amino group is reacted with an isocyanate group to obtain a crosslinked urethane resin having at least one structure represented by structural formula (Z102). Examples of the nitrogen-containing alicyclic group in structural formula (6) include a pyrrolidine group (5-membered), a pyrroline group (5-membered), a piperidine group (6-membered), an azepane group (7-membered), and an azocane group (8-membered). A specific example of the structural formula (6) is the structure shown in the following structural formula (6)-1.

[0071] [ka]

[0072] In structural formula (6)-1, Z15 to Z17 and d5 are defined as those in structural formula (6). As an example of a cation of an ionic compound capable of forming the structure represented by structural formula (6), a cation having a pyrrolidine group and a hydroxyl group is given below. 1-methyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-ethyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-butyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-methyl-1,2-bis(4-hydroxybutyl)pyrrolidinium cation; and derivatives thereof. Examples of the cation having an amino group include cations having a structure in which some or all of the hydroxyl groups of the above-mentioned cations are substituted with amino groups.

[0073] [ka]

[0074] In structural formulae (Z101) and (Z102), R10 and R11 each independently represent a linear or branched divalent hydrocarbon group. The hydrocarbon group is preferably a linear or branched alkylene group having 1 to 8 carbon atoms. The symbol "*" represents a bond to the nitrogen atom in structural formula (1) or a bond to a nitrogen atom in a nitrogen-containing heterocycle or a bond to a carbon atom in a nitrogen-containing heterocycle in structural formulas (2) to (6). The symbol "**" represents a bond to a carbon atom in a polymer chain constituting the resin having a cationic structure. As described above, the structure represented by structural formula (Z101) is a residue formed by the reaction of a hydroxyl group of a cation of the raw ionic compound with an isocyanate group. The structure represented by the structural formula (Z102) is a residue formed by reacting an amino group of a cation with an isocyanate group. The isocyanate group that reacts with a hydroxyl group or an amino group is preferably an isocyanate group of a binder resin.

[0075] The resin layer according to one embodiment of the present disclosure may contain carbon black together with the resin having a cationic structure. When the resin layer contains carbon black, the cationic structure in the resin is preferably a cationic structure having an aromatic ring as shown in the above structural formulas (2) to (3) and (5). This is because the π electrons on the aromatic ring interact with the π electrons of the carbon black, and the molecular mobility of the cationic structural portion can be further suppressed.

[0076] [Cross-linked acrylic resin] Crosslinked acrylic resins are formed by polymerization of acrylic monomers having an ether bond (-COC-). The acrylic monomers mentioned here do not only mean acrylic monomers but also methacrylic monomers. In other words, crosslinked acrylic resins are formed by polymerization of either acrylic monomers or methacrylic monomers, or both. The ether bond in the acrylic monomer is a -COC- bond other than the ester moiety, and is usually introduced as a polyoxyalkylene structure, such as ethylene oxide (EO) or propylene oxide (PO). In order to form an IPN structure with the crosslinked acrylic resin and the crosslinked urethane resin in the vicinity of the outer surface of the surface layer, as described above, the resin layer containing the crosslinked urethane is impregnated with a liquid acrylic monomer and cured. The type of acrylic monomer used here includes a polyfunctional monomer having a plurality of acryloyl groups or methacryloyl groups as functional groups in order to form a crosslinked structure. On the other hand, when the functional group is four or more, the viscosity of the acrylic monomer becomes significantly high, so that it is difficult to penetrate into the surface of the resin layer made of the crosslinked urethane resin, and as a result, it is difficult to form an IPN structure. Therefore, as the acrylic monomer, a monomer in which the total number of acryloyl groups and methacryloyl groups present in one molecule is two or three is preferable, and a bifunctional acrylic monomer in which the total number is two is more preferable. When these polyfunctional monomers are used, an IPN structure is effectively formed, so that the molecular mobility of the crosslinked urethane resin can be effectively suppressed. In addition, a monofunctional monomer may be combined as necessary.

[0077] The molecular weight of the acrylic monomer is preferably in the range of 200 to 750. By using a molecular weight in this range, an IPN structure is easily formed with respect to the network structure of the crosslinked urethane resin, and the molecular mobility of the crosslinked urethane resin can be further suppressed. As described above, the acrylic monomer is impregnated into the resin layer containing the crosslinked urethane resin. For this purpose, the acrylic monomer has an appropriate viscosity. That is, if the viscosity is high, it is difficult to impregnate, and if the viscosity is low, it is difficult to control the impregnation state. Therefore, the viscosity of the acrylic monomer is preferably 5.0 mPa·s or more and 140 mPa·s or less at 25°C. That is, one or more acrylic monomers satisfying the above-mentioned molecular weight and viscosity ranges are selected, impregnated into the resin layer, and polymerized to form an IPN structure of cross-linked urethane resin and cross-linked acrylic resin.

[0078] The method for polymerizing the acrylic monomer is not particularly limited, and any known method can be used, specifically, methods such as heating and ultraviolet irradiation can be used. For each polymerization method, a known radical polymerization initiator or ionic polymerization initiator can be used. Examples of the polymerization initiator in the case of polymerization by heating include peroxides such as 3-hydroxy-1,1-dimethylbutylperoxyneodecanoate, α-cumylperoxyneodecanoate, t-butylperoxyneoheptanoate, t-butylperoxypivalate, t-amylperoxynormaloctoate, t-butylperoxy2-ethylhexylcarbonate, dicumylperoxide, di-t-butylperoxide, di-t-amylperoxide, 1,1-di(t-butylperoxy)cyclohexane, and n-butyl-4,4-di(t-butylperoxy)valerate; Examples of azo compounds include 2,2-azobisbutyronitrile, 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-methylbutyronitrile), 1,1-azobis(cyclohexane-1-carbonitrile), 2,2-azobis[2-(2-imidazolin-2-yl)propane], 2,2-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2-azobis(N-butyl-2-methoxypropionamide), and dimethyl-2,2-azobis(isobutyrate).

[0079] Examples of the polymerization initiator when polymerizing by irradiation with ultraviolet light include 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methylpropane- 1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. These polymerization initiators may be used alone or in combination of two or more kinds. In addition, the amount of the polymerization initiator is preferably 0.5 parts by mass or more and 10 parts by mass or less, from the viewpoint of efficiently progressing the reaction, when the total amount of the compounds for forming the specific resin (e.g., compounds having a (meth)acryloyl group) is 100 parts by mass. The heating device and the ultraviolet ray irradiation device may be appropriately selected from known devices. As the light source for irradiating ultraviolet rays, for example, an LED lamp, a high-pressure mercury lamp, a metal halide lamp, a xenon lamp, and a low-pressure mercury lamp may be used. The integrated light amount required for polymerization may be appropriately adjusted depending on the type and amount of the compound and the polymerization initiator used. Examples of the acrylic monomer include bifunctional (meth)acrylates such as diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, PO-modified neopentyl glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate; and trifunctional (meth)acrylates such as trimethylolpropane ethoxy tri(meth)acrylate and glycerin propoxy tri(meth)acrylate.

[0080] [Crosslinked epoxy resin] The crosslinked epoxy resin is formed, for example, by polymerization of a glycidyl ether monomer having an ether bond (-COC-), and has a structural unit as shown in the following structural formula (7).

[0081] [ka]

[0082] (In structural formula (7), R represents a linear or branched divalent hydrocarbon.) In order for the crosslinked epoxy resin to form an IPN structure with the crosslinked urethane resin in the vicinity of the outer surface of the surface layer, as described above, there is a method in which a resin layer containing the crosslinked urethane is impregnated with a liquid glycidyl ether monomer and then cured. The type of glycidyl ether monomer used here includes a polyfunctional monomer having a plurality of glycidyl groups in order to form a crosslinked structure. On the other hand, when the functional group is four or more, the viscosity of the glycidyl ether monomer becomes significantly high, so that it is difficult to penetrate into the surface of the resin layer made of the crosslinked urethane resin, and as a result, it is difficult to form an IPN structure. Therefore, as the glycidyl ether monomer, a monomer having two or three glycidyl groups in one molecule is preferable, and more preferably, a bifunctional glycidyl ether monomer having two glycidyl groups is mentioned. When these polyfunctional monomers are used, an IPN structure is effectively formed, so that the molecular mobility of the crosslinked urethane resin can be effectively suppressed. In addition, a monofunctional monomer may be combined as necessary. The molecular weight of the glycidyl ether monomer is preferably in the range of 200 to 750. By using a molecular weight in this range, an IPN structure is easily formed in the network structure of the crosslinked urethane resin, and the molecular mobility of the crosslinked urethane resin can be further suppressed.

[0083] As described above, the glycidyl ether monomer is impregnated into the resin layer containing the crosslinked urethane resin. To achieve this, the glycidyl ether monomer must have an appropriate viscosity. That is, if the viscosity is high, impregnation is difficult, and if the viscosity is low, it is difficult to control the impregnation state. Therefore, the viscosity of the glycidyl ether monomer is preferably 5.0 mPa·s or more and 140 mPa·s or less at 25°C. That is, one or more glycidyl ether monomers satisfying the above-mentioned molecular weight and viscosity ranges are selected, impregnated into a resin layer, and polymerized to form an IPN structure of a crosslinked urethane resin and a crosslinked epoxy resin. The method for polymerizing the glycidyl ether monomer is not particularly limited, and any known method can be used. As for the heating device and the ultraviolet ray irradiation device, as in the case of the acrylic monomer, known devices can be appropriately used. As the light source for irradiating ultraviolet rays, for example, an LED lamp, a high-pressure mercury lamp, a metal halide lamp, a xenon lamp, and a low-pressure mercury lamp can be used. The integrated light amount required for polymerization can be appropriately adjusted depending on the type and the amount of the compound and the polymerization initiator used.

[0084] As the glycidyl ether monomer, alkyleneoxy glycidyl ether is preferably used. Specific examples are given below. Ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,5-pentanediol glycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether.

[0085] <How to confirm interpenetrating polymer network structure (IPN)> The formation of an IPN structure can be confirmed by a method using solvent extraction or by checking the shift in the glass transition point before and after the formation of the IPN structure. In the present disclosure, however, confirmation is performed based on the peak top temperature of a thermal chromatogram. Due to the mutual entanglement of the polymers, the thermal decomposition temperature, i.e., the peak top temperature of the thermal chromatogram, shifts to the higher temperature side. Therefore, the presence or absence of an IPN structure can be confirmed by checking the magnitude relationship of the peak top temperature of the thermal chromatogram with and without the formation of an IPN structure. That is, when comparing the peak top of the crosslinked acrylic resin or crosslinked epoxy resin that forms an IPN structure with the crosslinked urethane resin with that of the crosslinked acrylic resin or epoxy resin when it exists alone, the former has a peak top temperature on the higher temperature side. Therefore, when comparing the peak top temperatures of the thermal chromatogram derived from the second resin before and after the crosslinked urethane resin is decomposed and removed, if the peak top temperature before the crosslinked urethane resin is decomposed and removed is higher, it can be confirmed that an IPN structure is formed. The term "thermal chromatogram" used here refers to a mass spectrum called an ion chromatogram, which can be obtained by microsampling mass spectrometry. An overview of microsampling mass spectrometry is given below.

[0086] <Microsampling mass spectrometry> First, a region of the electrophotographic member to be measured is cut into a thin piece using a cryomicrotome to prepare a sample. In this disclosure, as shown in FIG. 5, a sample is prepared from two regions called a first region 41 and a second region 42. The first region is a region from the outer surface of the surface layer 43 to a depth of 0.1 μm, and the second region is a region with a thickness of 0.1 μm from the back surface of the surface layer 43 (the surface facing the conductive substrate 44) toward the outer surface. From each region of the surface layer, a sample with a square of 100 μm and a width of 0.1 μm in the depth direction is prepared. For the measurement, an ion trap mass spectrometer mounted on a gas chromatography mass spectrometer ("Polaris Q" (product name, Thermo Electron) is used. A sample is fixed to a filament at the tip of the probe and directly inserted into the ionization chamber. The sample is then rapidly heated from room temperature to 1000°C at a constant heating rate. The sample is decomposed and evaporated by heating, ionized by irradiation with an electron beam, and detected by a mass spectrometer. At this time, under conditions of a constant heating rate, a thermal chromatogram similar to the TG-MS (thermogravimetric-mass simultaneous analysis) method is obtained, which has a mass spectrum called a total ion chromatogram (TIC). In addition, a thermal chromatogram for a fragment of a specified mass can be obtained, so that the peak temperature of the thermal chromatogram corresponding to the decomposition temperature of the desired molecular structure can be obtained. The peak temperature of the thermal chromatogram is correlated with the crosslinking structure in the resin structure, and the denser the crosslinking, the higher the peak temperature shifts to the higher temperature side. In the electrophotographic member according to the present embodiment, the first resin and the second resin form an IPN structure in the vicinity of the outer surface of the surface layer, so that the first resin and the second resin are held in close proximity even in a high-temperature environment. This allows the interaction between the first resin and the second resin due to their intermolecular forces to be exerted even in a high-temperature environment, so that leakage of the charge of the toner particles is suppressed even in a high-temperature and high-humidity environment. The second resin forms an IPN structure with the first resin by confirming that there is a difference in peak temperature of the thermal chromatogram of the fragment derived from the second resin before and after the first resin in the composition is decomposed and removed. That is, the peak top temperature of the thermal chromatogram derived from the crosslinked acrylic resin or the crosslinked epoxy resin measured from the first sample sampled from the above-mentioned first region is defined as A1 (°C). Also, the peak top temperature of the thermal chromatogram derived from the crosslinked acrylic resin or the crosslinked epoxy resin measured from the second sample obtained by decomposing the crosslinked urethane resin contained in the first sample is defined as A2 (°C). When A1 and A2 satisfy the relationship shown in the following relational formula (1), the molecular mobility of the cationic structural part on the outer surface of the surface layer is effectively suppressed, and the transfer of charge from the toner particles can be suppressed. A1>A2 (1). Also, T1 is the peak top temperature (°C) of the thermal chromatogram derived from the cross-linked urethane resin in the first region, and T2 is the peak top temperature (°C) of the thermal chromatogram derived from the cross-linked urethane resin contained in the second region. In this case, it is preferable to satisfy the following relational expression (2). T1>T2 (2). Not satisfying the relational expression (2) means that the molecular mobility of the crosslinked urethane resin is suppressed not only on the outer surface of the surface layer but also throughout the entire surface layer. When the relational expression (2) is not satisfied, the electrophotographic member tends to charge up even under high temperature and high humidity conditions, which is unfavorable to fog.

[0087] [Anion] Examples of the anion include a fluorinated sulfonate anion, a fluorinated carboxylate anion, a fluorinated sulfonylimide anion, a fluorinated sulfonylmethide anion, a fluorinated alkylfluoroborate anion, a fluorinated alkylfluorophosphate anion, a halide ion, a carboxylate anion, a sulfonate anion, a tetrafluoroborate anion, a hexafluorophosphate anion, a hexafluoroarsenate anion, a hexafluoroantimonate anion, a dicyanamide anion, a bis(oxalato)borate anion, a nitrate anion, and a perchlorate anion. Examples of the fluorinated sulfonate anion include a trifluoromethanesulfonate anion, a fluoromethanesulfonate anion, a perfluoroethylsulfonate anion, a perfluoropropylsulfonate anion, a perfluorobutylsulfonate anion, a perfluoropentylsulfonate anion, a perfluorohexylsulfonate anion, and a perfluorooctylsulfonate anion. Examples of the fluorinated carboxylate anion include a trifluoroacetate anion, a perfluoropropionate anion, a perfluorobutyrate anion, a perfluorovalerate anion, and a perfluorocaproate anion. Examples of the fluorinated sulfonylimide anion include anions such as trifluoromethanesulfonylimide anion, perfluoroethylsulfonylimide anion, perfluoropropylsulfonylimide anion, perfluorobutylsulfonylimide anion, perfluoropentylsulfonylimide anion, perfluorohexylsulfonylimide anion, perfluorooctylsulfonylimide anion, and fluorosulfonylimide anion, and cyclic anions such as cyclohexafluoropropane-1,3-bis(sulfonyl)imide. Examples of the fluorinated sulfonylmethide anion include trifluoromethanesulfonylmethide anion, perfluoroethylsulfonylmethide anion, perfluoropropylsulfonylmethide anion, perfluorobutylsulfonylmethide anion, perfluoropentylsulfonylmethide anion, perfluorohexylsulfonylmethide anion, and perfluorooctylsulfonylmethide anion. Examples of the fluorinated alkylfluoroborate anion include a trifluoromethyltrifluoroborate anion and a perfluoroethyltrifluoroborate anion. Examples of the fluorinated alkyl fluorophosphate anion include tris-trifluoromethyl-trifluorophosphate anion and tris-perfluoroethyl-trifluorophosphate anion. Examples of the halide ion include a fluoride ion, a chloride ion, a bromide ion, and an iodide ion. Examples of the carboxylate anion include alkylcarboxylate anions such as acetate anion, propionate anion, butyrate anion and hexanoate anion, and aromatic carboxylate anions such as benzoate anion. The anion may have one or more substituents, such as a hydrocarbon group having 1 to 30 carbon atoms, a halogen group such as fluorine, chlorine, bromine and iodine, an alkoxy group such as a methoxy group and an ethoxy group, an amide group and a cyano group, and a substituent containing a hetero atom, and a haloalkyl group such as a trifluoromethyl group. Examples of the sulfonate anion include alkylsulfonate anions such as methanesulfonate anion and ethanesulfonate anion, and aromatic sulfonate anions such as benzenesulfonate and para-toluenesulfonate anion, which may be substituted with one or more substituents, such as a hydrocarbon group having 1 to 30 carbon atoms, a halogen group such as fluorine, chlorine, bromine, and iodine, an alkoxy group such as a methoxy group and an ethoxy group, an amide group, a substituent containing a hetero atom such as a cyano group, and a haloalkyl group such as a trifluoromethyl group.

[0088] [Conductive agent] In addition to the ion-conductive structure due to the cations and anions in the resin, the surface layer may contain a conductivity imparting agent such as an electronic conductive substance or other ionic compounds to the extent that the effect achieved by the configuration according to the present disclosure is not impaired. The volume resistivity of the surface layer is preferably 10 3 Ωcm or more 10 11 Ωcm or less, more preferably 10 4 Ωcm or more 10 10 The resistance is adjusted to Ωcm or less. As the electronically conductive material, a conductive filler described below can be used, but conductive carbon is preferred because the conductivity can be easily controlled with a small amount.

[0089] These conductivity imparting agents are used in an amount necessary to adjust the surface layer to an appropriate volume resistivity as described above, and are usually used in an amount within the range of 0.5 parts by mass to 50 parts by mass per 100 parts by mass of the binder resin.

[0090] [Filler] Further, a filler may be contained for the purpose of enhancing the reinforcing effect of the surface layer. Examples of insulating fillers include: quartz fine powder, silica particles, diatomaceous earth, zinc oxide, basic magnesium carbonate, activated calcium carbonate, magnesium silicate, aluminum silicate, titanium dioxide, talc, mica powder, aluminum sulfate, calcium sulfate, barium sulfate, glass fiber, organic reinforcing agent, organic filler. The surface of these fillers may be hydrophobized by treating with an organic silicon compound, for example, polydiorganosiloxane. As the insulating filler, silica particles are preferably used because of their good uniform dispersion in the surface layer. Furthermore, among silica particles, silica particles whose surfaces have been hydrophobized are particularly preferably used. The content of silica particles is preferably 0.5% by mass or more and 20% by mass or less with respect to 100 parts by mass of the resin component forming the surface layer. Considering the reinforcing performance and electrical conductivity of the surface layer, the primary particle diameter of the silica particles is preferably in the range of 10 nm to 120 nm in terms of the number average primary particle diameter. Also, it is more preferably in the range of 15 nm to 80 nm, and particularly preferably in the range of 15 nm to 40 nm. The number average primary particle diameter is measured as follows. Silica particles are observed with a scanning electron microscope, and the particle diameters of 100 particles in the field of view are measured to determine the average particle diameter. Examples of the conductive filler include the following: carbon-based materials such as carbon black and graphite; metals or alloys such as aluminum, silver, gold, tin-lead alloy, and copper-nickel alloy; metal oxides such as zinc oxide, titanium oxide, aluminum oxide, tin oxide, antimony oxide, indium oxide, and silver oxide; and materials in which various fillers are plated with conductive metals such as copper, nickel, and silver. Carbon black is particularly preferably used as the conductive filler because it is easy to control the conductivity and is inexpensive. Among them, those having a relatively small primary particle size and maintaining a hydrophobic tendency are particularly preferably used because of good uniform dispersion in the surface layer. Considering the reinforcing performance and conductivity of the surface layer, the primary particle size of the carbon black is preferably in the range of 20 nm or more and 60 nm or less in number average primary particle size. As for the surface characteristics of carbon black, it is preferable that the pH is 3.0 or more and 8.0 or less. In addition, the content of carbon black is preferably 5% by mass or more and 45% by mass or less with respect to 100 parts by mass of the resin component forming the surface layer.

[0091] Furthermore, when carbon black is contained in the elastic layer according to the present embodiment, it is preferable to use carbon black having a volatile content of 0.4% or more, preferably 0.6% or more. The volatile content of carbon black is measured according to the provisions of Japanese Industrial Standards (JIS) K6221 (1982) "Testing method for carbon black for rubber". The volatile content of carbon black is a parameter that correlates with the amount of functional groups present on the surface of the carbon black. The higher the volatile content, the greater the amount of functional groups present on the surface of the carbon black. Surface functional groups on carbon black usually include carboxyl groups and hydroxyl groups. Therefore, the higher the volatile content of carbon black, i.e., the more surface functional groups, the more acidic the carbon black is.

[0092] A crosslinked urethane resin has soft segments and hard segments, the soft segments being based on the main chain skeleton of the raw material polyol, and the hard segments being formed by the aggregation of urethane bonds in the molecule through hydrogen bonds. In other words, in a crosslinked urethane resin, the hard segments contain a relatively large number of urethane bonds. It is preferable that the coating material for forming the resin layer that becomes the surface layer contains polyol and polyisocyanate, which are raw materials for cross-linked urethane resin, and carbon black with a volatile content of 0.4% or more. When the resin layer is formed using such a coating material, the carbon black forms hydrogen bonds with the urethane bond while forming the cross-linked urethane resin. As a result, it is possible to suppress the molecular mobility of the urethane structure portion at a high level. Carbon black with a volatile content of 0.4% or more is commercially available, and examples thereof include "SUNBLACK" (registered trademark) carbon black for coloring (manufactured by Asahi Carbon Co., Ltd.) and "Mitsubishi" (registered trademark) carbon black (manufactured by Mitsubishi Chemical Corporation).

[0093] [Other ingredients] In addition to those described above, the surface layer may contain various additives such as a crosslinking agent, a crosslinking aid, a plasticizer, a filler, an extender, a vulcanizing agent, a vulcanization aid, an antioxidant, an antiaging agent, a processing aid, a dispersant, and a leveling agent, as long as the additives do not impair the above functions.

[0094] [Electrophotographic process cartridge and electrophotographic image forming apparatus] The electrophotographic image forming apparatus according to the present disclosure is an apparatus having an image carrier for carrying an electrostatic latent image, a charging device for primarily charging the image carrier, an exposure device for forming an electrostatic latent image on the primarily charged image carrier, a developing device for developing the electrostatic latent image with toner to form a toner image, and a transfer device for transferring the toner image to a transfer material. Fig. 3 is a cross-sectional view showing an outline of the electrophotographic image forming apparatus according to the present disclosure. Fig. 4 is an enlarged sectional view of a process cartridge to be mounted in the electrophotographic image forming apparatus of Fig. 3. This process cartridge incorporates an image carrier 21 such as a photosensitive drum, a charging device having a charging member 22, a developing device having a developing member 24, and a cleaning device having a cleaning member 30. The process cartridge is configured to be detachably mounted in the main body of the electrophotographic image forming apparatus of Fig. 3. The image carrier 21 is uniformly charged (primary charging) by a charging member 22 connected to a bias power supply (not shown). The charged potential of the image carrier 21 at this time is -800V or more and -400V or less. Next, the image carrier 21 is irradiated with exposure light 23 for writing an electrostatic latent image by an exposure device (not shown), and an electrostatic latent image is formed on its surface. Either LED light or laser light can be used as the exposure light 23. The surface potential of the image carrier 21 in the exposed portion is -200V or more and -100V or less. Next, the developing member 24 applies (develops) negatively charged toner to the electrostatic latent image, forming a toner image on the image carrier 21 and converting the electrostatic latent image into a visible image. At this time, a voltage of -500V to -300V is applied to the developing member 24 by a bias power source (not shown). The developing member 24 contacts the image carrier 21 with a nip width of 0.5mm to 3mm. In the process cartridge according to the present disclosure, the toner supply roller 25 is rotatably contacted with the developing member 24 on the upstream side of the rotation of the developing member 24 with respect to the contact portion between the developing blade 26, which is a toner regulating member, and the developing member 24. The toner image developed on the image carrier 21 is primarily transferred to the intermediate transfer belt 27. A primary transfer member 28 is in contact with the rear surface of the intermediate transfer belt 27, and a voltage of +100 V or more and +1500 V or less is applied to the primary transfer member 28 to primarily transfer the negative polarity toner image from the image carrier 21 to the intermediate transfer belt 27. The primary transfer member 28 may be in the form of a roller or a blade.

[0095] When the electrophotographic image forming apparatus is a full-color image forming apparatus, the above-mentioned charging, exposure, development, and primary transfer processes are performed for each of the colors yellow, cyan, magenta, and black. To this end, in the electrophotographic image forming apparatus shown in FIG. 3, a total of four process cartridges, one for each color, containing toner, are detachably mounted in the main body of the electrophotographic image forming apparatus. The above-mentioned charging, exposure, development, and primary transfer processes are performed sequentially with a predetermined time difference, and a state in which four color toner images are superimposed on the intermediate transfer belt 27 to express a full-color image is created. The toner image on the intermediate transfer belt 27 is transported to a position facing the secondary transfer member 29 as the intermediate transfer belt 27 rotates. A recording sheet is transported between the intermediate transfer belt 27 and the secondary transfer member 29 along a recording sheet transport route 32 at a predetermined timing, and the toner image on the intermediate transfer belt 27 is transferred to the recording sheet by applying a secondary transfer bias to the secondary transfer member 29. At this time, the bias voltage applied to the secondary transfer member 29 is +1000V or more and +4000V or less. The recording sheet to which the toner image has been transferred by the secondary transfer member 29 is transported to a fixing device 31, where the toner image on the recording sheet is melted and fixed on the recording sheet, and the recording sheet is then discharged outside the electrophotographic image forming apparatus, completing the printing operation. In addition, any toner remaining on the image carrier 21 without being transferred from the image carrier 21 to the intermediate transfer belt 27 is scraped off by a cleaning member 30 for cleaning the surface of the image carrier 21, and the surface of the image carrier 21 is cleaned. EXAMPLES

[0096] The present disclosure will be described in more detail below by taking a developing roller as an example and giving specific examples, although the technical scope of the present disclosure as an electrophotographic member is not limited thereto.

[0097] First, an ionic compound, which is a raw material of the resin contained in the resin layer of the electrophotographic member, was synthesized. <Synthesis of ionic compounds> (Ionic Compound I-1) 15.0 g of bis(2-hydroxyethyl)dimethylammonium chloride (Tokyo Chemical Industry Co., Ltd.) was dissolved in 40.0 g of ion-exchanged water. Next, 37.7 g of lithium bis(pentafluoroethanesulfonyl)imide (Kishida Chemical Co., Ltd.) was dropped as an anion exchange reagent (hereinafter referred to as "anion raw material") dissolved in 60 g of ion-exchanged water over 30 minutes, and then stirred at 30°C for 2 hours. The obtained reaction solution was subjected to extraction operation twice using 100.0 g of ethyl acetate. Then, the separated ethyl acetate layer was washed three times using 60 g of ion-exchanged water. Then, ethyl acetate was distilled off under reduced pressure to obtain ionic compound I-1, whose anion is bis(pentafluoroethanesulfonyl)imide anion. Ionic compound I-1 is a compound represented by the following formula.

[0098] [ka]

[0099] (Ionic Compound I-2) 15.0 g of diethylenetriamine (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved in 35.0 g of tetrahydrofuran. Next, the reaction system was placed under a nitrogen atmosphere and cooled on ice. Then, 45.5 g of methyl iodide (manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in 80.0 g of tetrahydrofuran was added dropwise over 30 minutes. After heating and refluxing the reaction solution for 12 hours, 100 ml of water was added, and the solvent was distilled off under reduced pressure. 100 ml of ethanol was added to the residue, stirred at room temperature, insoluble matter was removed by celite filtration, and the solvent was distilled off again under reduced pressure. The obtained product was dissolved in 160 ml of pure water, and 37.7 g of sodium heptafluorobutyrate (manufactured by Wako Pure Chemical Industries, Ltd.) was added as an anion raw material, and the mixture was stirred at room temperature for 1 hour. The obtained reaction solution was subjected to extraction twice using 100.0 g of ethyl acetate. Next, the separated ethyl acetate layer was washed three times using 60 g of ion-exchanged water. Subsequently, ethyl acetate was distilled off under reduced pressure to obtain ionic compound I-2, which is a compound represented by the following formula:

[0100] [ka]

[0101] (Ionic Compound I-3) 15.0 g of 2-(2-methyl-1H-imidazol-1-yl)ethanol (Sigma-Aldrich) and 9.2 g of 60% sodium hydride dispersion in liquid paraffin (Tokyo Chemical Industry Co., Ltd.) were dissolved in 80.0 g of tetrahydrofuran. 14.5 g of ethyl bromide (Showa Kagaku Co., Ltd.) dissolved in 80.0 g of tetrahydrofuran was added dropwise to the mixture over 30 minutes at room temperature, and the mixture was heated and refluxed at 85°C for 12 hours. Next, 100 ml of water was added to the reaction solution, and the solvent was distilled off under reduced pressure. 200 ml of ethanol was added to the residue, stirred at room temperature, and insoluble matter was removed by filtration through Celite, and the solvent was distilled off again under reduced pressure. The resulting product was dissolved in 100 ml of pure water, and 38.2 g of lithium N,N-bis(trifluoromethanesulfonyl)imide (trade name: EF-N115, Mitsubishi Materials Electronic Chemicals Co., Ltd.) was added as an anion raw material, and the mixture was stirred at room temperature for 1 hour. 100ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 80g of ion-exchanged water. Next, ethyl acetate was distilled off under reduced pressure to obtain ionic compound I-3. Ionic compound I-3 is a compound represented by the following formula.

[0102] [ka]

[0103] (Ionic Compound I-4) Under a nitrogen atmosphere, 15.0 g of imidazole (manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) and 9.2 g of sodium hydride 60% liquid paraffin dispersion (manufactured by Tokyo Chemical Industry Co., Ltd.) were dissolved in 60.0 g of tetrahydrofuran. 60.7 g of 2-bromoethanol (manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in 80.0 g of tetrahydrofuran was added dropwise to the mixture over 30 minutes at room temperature, and the mixture was heated and refluxed at 85°C for 12 hours. Next, 100 ml of water was added to the reaction solution, and the solvent was distilled off under reduced pressure. 200 ml of ethanol was added to the residue, stirred at room temperature, and insoluble matter was removed by celite filtration, and the solvent was distilled off again under reduced pressure. The obtained product was dissolved in 200 ml of pure water, and 69.6 g of lithium N,N-bis(trifluoromethanesulfonyl)imide (trade name: EF-N115, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) was added as an anion raw material, and the mixture was stirred at room temperature for 1 hour. 200ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 120g of ion-exchanged water. Next, ethyl acetate was distilled off under reduced pressure to obtain ionic compound I-4. Ionic compound I-4 is a compound represented by the following formula.

[0104] [ka]

[0105] (Ionic Compound I-5) Under a nitrogen atmosphere, 15.0 g of (1H-imidazol-2-yl)ethanol (Sigma-Aldrich) and 9.2 g of 60% sodium hydride dispersion in liquid paraffin (Tokyo Chemical Industry Co., Ltd.) were dissolved in 60.0 g of tetrahydrofuran. 42.1 g of 2-bromoethanol (Tokyo Chemical Industry Co., Ltd.) dissolved in 80.0 g of tetrahydrofuran was added dropwise at room temperature over 30 minutes, and the mixture was heated and refluxed at 85°C for 12 hours. Next, 100 ml of water was added to the reaction solution, and the solvent was distilled off under reduced pressure. 200 ml of ethanol was added to the residue, stirred at room temperature, and insoluble matter was removed by filtration through Celite, and the solvent was distilled off again under reduced pressure. The obtained product was dissolved in 200 ml of pure water, and 48.3 g of lithium N,N-bis(trifluoromethanesulfonyl)imide (trade name: EF-N115, Mitsubishi Materials Electronic Chemicals Co., Ltd.) was added as an anion raw material, and the mixture was stirred at room temperature for 1 hour. 200ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 120g of ion-exchanged water. Next, ethyl acetate was distilled off under reduced pressure to obtain ionic compound I-5. Ionic compound I-5 is a compound represented by the following formula.

[0106] [ka]

[0107] (Ionic Compound I-6) 15.0 g of (5-methylpyrazin-2-yl)methanol (Sigma-Aldrich) and 9.2 g of sodium hydride 60% liquid paraffin dispersion (Tokyo Chemical Industry Co., Ltd.) were dissolved in 80.0 g of tetrahydrofuran. 18.9 g of methyl iodide (Tokyo Chemical Industry Co., Ltd.) dissolved in 80.0 g of tetrahydrofuran was added dropwise to the mixture over 30 minutes at room temperature, and the mixture was heated and refluxed at 85°C for 12 hours. Next, 100 ml of water was added to the reaction solution, and the solvent was distilled off under reduced pressure. 200 ml of ethanol was added to the residue, stirred at room temperature, and insoluble matter was removed by filtration through Celite, and the solvent was distilled off again under reduced pressure. The obtained product was dissolved in 100 ml of pure water, and 59.8 g of potassium tris(trifluoromethanesulfonyl)methide (trade name: K-TFSM; Central Glass Co., Ltd.) was added as an anion raw material, and the mixture was stirred at room temperature for 1 hour. 100ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 80g of ion-exchanged water. Next, ethyl acetate was distilled off under reduced pressure to obtain ionic compound I-6. Ionic compound I-6 is a compound represented by the following formula.

[0108] [ka]

[0109] (Ionic Compound I-7) 15.0 g of N,N'-bis(2-hydroxyethyl)-2,5-dimethylpiperazine (Sigma-Aldrich) and 9.2 g of sodium hydride 60% liquid paraffin dispersion (Tokyo Chemical Industry Co., Ltd.) were dissolved in 80.0 g of tetrahydrofuran. 11.6 g of methyl iodide (Tokyo Chemical Industry Co., Ltd.) dissolved in 80.0 g of tetrahydrofuran was added dropwise at room temperature over 30 minutes, and the mixture was heated to reflux at 85°C for 12 hours. Next, 100 ml of water was added to the reaction solution, and the solvent was distilled off under reduced pressure. 200 ml of ethanol was added to the residue, stirred at room temperature, and insoluble matter was removed by celite filtration, and the solvent was again distilled off under reduced pressure. The obtained product was dissolved in 100 ml of pure water, and 23.4 g of lithium N,N-bis(trifluoromethanesulfonyl)imide (product name: EF-N115, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) was added as an anion raw material, and the mixture was stirred at room temperature for 1 hour. 100 ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 80 g of ion-exchanged water. Next, ethyl acetate was distilled off under reduced pressure to obtain ionic compound I-7. Ionic compound I-7 is a compound represented by the following formula.

[0110] [ka]

[0111] (Ionic Compound I-8) 15.0 g of 4-pyridin-4-yl-butan-1-ol (Sigma-Aldrich) was dissolved in 45.0 g of acetonitrile, and 16.7 g of 4-bromo-1-butanol (Tokyo Chemical Industry Co., Ltd.) was added dropwise at room temperature over 30 minutes, and the mixture was heated to reflux at 90°C for 12 hours. Next, the reaction solution was cooled to room temperature, and acetonitrile was distilled off under reduced pressure. The resulting concentrate was washed with 30.0 g of diethyl ether, and the supernatant liquid was removed by separation. The washing and separation operations were repeated three times to obtain a residue. Furthermore, the resulting residue was dissolved in 110.0 g of dichloromethane, and then 31.4 g of anion raw material: lithium N,N-bis(trifluoromethanesulfonyl)imide (trade name: EF-N115, Mitsubishi Materials Electronic Chemicals Co., Ltd.) dissolved in 40.0 g of ion-exchanged water was added dropwise over 30 minutes, and the mixture was stirred at 30°C for 12 hours. The obtained solution was separated, and the organic layer was washed three times with 80.0 g of ion-exchanged water. Then, dichloromethane was distilled off under reduced pressure to obtain ionic compound I-8. Ionic compound I-8 is a compound represented by the following formula.

[0112] [ka]

[0113] (Ionic Compound I-9) 15.0 g of 2-(2-hydroxyethyl)-1-methylpyrrolidine (Tokyo Chemical Industry Co., Ltd.) and 13.5 g of sodium hydride 60% liquid paraffin dispersion (Tokyo Chemical Industry Co., Ltd.) were dissolved in 65.0 g of tetrahydrofuran. Next, the reaction system was placed under a nitrogen atmosphere and cooled on ice. Then, 16.0 g of 2-bromoethanol (Tokyo Chemical Industry Co., Ltd.) dissolved in 40.0 g of tetrahydrofuran was added dropwise over 30 minutes. After the reaction solution was heated under reflux for 12 hours, 100 ml of water was added and the solvent was distilled off under reduced pressure. 80 ml of ethanol was added to the residue and stirred at room temperature. Insoluble matter was removed by filtration through Celite, and the solvent was again distilled off under reduced pressure. The obtained product was dissolved in 160 ml of pure water, and 36.7 g of lithium N,N-bis(trifluoromethanesulfonyl)imide (product name: EF-N115, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) was added as an anion raw material, and the mixture was stirred at room temperature for 1 hour. 70 ml of chloroform was added to the reaction solution, and 40 ml of a 5% by mass aqueous solution of sodium carbonate was added, and the mixture was stirred for 30 minutes, and then separated. The chloroform layer was washed three times with 50 g of ion-exchanged water. Next, chloroform was distilled off under reduced pressure to obtain ionic compound I-9. Ionic compound I-9 is a compound represented by the following formula.

[0114] [ka]

[0115] Table 1 shows the structure of each ionic compound used in the examples and the relationship between R1 to R9 and Z1 to Z17 in each structural formula.

[0116] [Table 1]

[0117] Example 1 [Preparation of conductive substrate] A primer (product name: DY35-051, manufactured by Dow Corning Toray Co., Ltd.) was applied to a SUS304 core bar with an outer diameter of 6 mm and a length of 270 mm, and the core bar was heated for 20 minutes at a temperature of 150° C. This core bar was placed concentrically in a cylindrical mold with an inner diameter of 12.0 mm. As the material for the intermediate layer, the materials shown in Table 2 below were mixed in a kneader (product name: Trimix TX-15, manufactured by Inoue Seisakusho Co., Ltd.) to form an addition type silicone rubber composition, which was then poured into a mold heated to a temperature of 115° C. After the material was poured, it was heated and molded at a temperature of 120° C. for 10 minutes, cooled to room temperature, and then demolded from the mold to obtain a conductive base body (elastic roller) in which a 3.0 mm-thick intermediate layer was formed on the outer periphery of a core metal.

[0118] [Table 2]

[0119] [Surface treatment of conductive substrate] As shown in Fig. 2, four conductive substrates 44 were arranged concentrically around an excimer UV lamp 12 attached to a lamp holder 11 with a built-in water-cooled heat sink. Thereafter, the conductive substrates 44 were irradiated with excimer light from the excimer UV lamp 12 while rotating at 60 rpm, to perform surface treatment on the intermediate layer 3. At this time, the illuminance of the excimer UV lamp 12 was 25 mW / cm on the surface of the intermediate layer 3. 2 The irradiation amount was set to 150 mJ / cm in terms of cumulative light intensity. 2 The surface was treated so that

[0120] [Formation of surface layer] In forming the surface layer, first, a resin layer was formed. As the material for the resin layer, the materials in Table 3 below, other than the roughness-forming particles, were stirred and mixed. Then, it was dissolved in methyl ethyl ketone (manufactured by Kishida Chemical Co., Ltd.) so that the solid content concentration became 30% by mass, mixed, and then uniformly dispersed with a sand mill. Methyl ethyl ketone was added to this mixed solution to adjust the solid content concentration to 25% by mass, and the materials shown in the column of the roughness-forming particles in Table 2 were added, followed by stirring and dispersing with a ball mill to obtain a paint 1 for the resin layer. The elastic roller was immersed in this paint and applied so that the film thickness of the resin layer after drying became about 15 μm. Then, it was heated at 130 °C for 60 minutes to dry and cure the coating film to form a resin layer.

[0121]

Table 3

[0122] Subsequently, the impregnation and curing treatment of the acrylic monomer were carried out by the following method. As the material for the impregnation treatment liquid for the impregnation treatment, the materials shown in Table 4 below were dissolved and mixed. The elastic roller with the resin layer formed was immersed in this impregnation treatment liquid for 2 seconds for treatment to impregnate the acrylic monomer component. Then, it was air-dried at room temperature for 30 minutes and dried at 90 °C for 1 hour to volatilize the solvent. While rotating the dried elastic roller, ultraviolet rays were irradiated so that the integrated light quantity became 15000 mJ / cm 2 to cure the acrylic monomer and form a surface layer. As the ultraviolet irradiation device, a high-pressure mercury lamp (product name: Handy Type UV Curing Device, model: MDH2501N-02, manufactured by Marionetwork Co., Ltd.) was used.

[0123]

Table 4

[0124] The following evaluations were performed on the obtained developing roller. [Evaluation Method] <Measurement of T1, T2, A1, A2> The thermal chromatograms of the samples sampled from each of the first and second regions were obtained by the above-mentioned microsampling mass spectrometry. From the obtained thermal chromatograms, the peak top temperatures T1 and T2 of the thermal chromatograms originating from the crosslinked urethane resin in each of the first and second regions were obtained. In addition, the peak top temperature A1 of the thermal chromatogram originating from the crosslinked acrylic resin or the crosslinked epoxy resin was obtained from the first sample in the first region, and further, the peak top temperature A2 of the thermal chromatogram originating from the crosslinked acrylic resin or the crosslinked epoxy resin measured from the second sample obtained by decomposing the crosslinked urethane resin contained in the first sample was obtained. For the second region, a rubber roll mirror finisher (product name: SZC, manufactured by Mizuguchi Seisakusho Co., Ltd.) is used to polish and remove the roller surface to a predetermined depth, and the newly exposed surface is similarly cut into a thin section using a microtome. Furthermore, a sample for microsampling mass spectrometry (third sample) was collected from the thin section. A2 is a value obtained by performing microsampling mass spectrometry on the second sample obtained after decomposing the crosslinked urethane by the pyridine decomposition method described below. Each value is a value obtained by arithmetically averaging each peak temperature obtained by five measurements. The results are shown in Table 8.

[0125] <Pyridine decomposition method> The pyridine decomposition method is a method for selectively decomposing urethane bonds. By performing the pyridine decomposition method on a sample having an IPN structure of crosslinked acrylic resin or crosslinked epoxy resin and crosslinked urethane resin, it is possible to obtain crosslinked acrylic resin or crosslinked epoxy resin after removing the structure derived from the crosslinked urethane, and to capture the change in peak temperature of the thermal chromatogram due to the presence or absence of the IPN structure. Specifically, the pyridine decomposition method was performed as follows. Using a microtome, a sample was cut out from the surface of the developing roller at a thickness of 0.1 μm, and 500 mg of the sample was collected. 0.5 mL of a mixture of pyridine (manufactured by Wako Pure Chemical Industries, Ltd.) and water in a ratio of 3:1 was added to the obtained sample, and the urethane bond was decomposed by heating at 130° C. for 15 hours in a closed container made of fluororesin (Teflon (registered trademark)) with a stainless steel jacket. The pyridine was removed by treating the obtained decomposition product under reduced pressure. The sample thus obtained was subjected to the above-mentioned microsampling mass spectrometry to obtain the value of A2.

[0126] <Measurement of volatile content of carbon black> In a flask equipped with a Dimroth filter, 10 parts by mass of the surface layer peeled off from the developing roller, 100 parts by mass of diethanolamine (manufactured by Tokyo Chemical Industry Co., Ltd.) as a decomposition agent, and 0.5 parts by mass of pure water were added and heated to reflux at 160°C for 20 hours while stirring. 25 parts by mass of methyl ethyl ketone was added to the solution after the reaction, and centrifuged. The solution was further washed twice with 80 parts by mass of methyl ethyl ketone, centrifuged, and dried under reduced pressure to obtain carbon black contained in the surface layer. 1.5 g of the carbon black thus obtained was collected, and the volatile content of this carbon black was measured according to the provisions of Japanese Industrial Standards (JIS) K6221 (1982) "Test method for carbon black for rubber". Specifically, the carbon black was placed in a crucible, heated at 950°C for 7 minutes, and after cooling in air, the mass was measured and the amount of weight loss was calculated. The amount of weight loss relative to the original mass, expressed in mass, was taken as the volatile content of the sample. The results are shown in Table 8.

[0127] <Fogging evaluation under high temperature and humidity conditions> Fog is an image defect that appears like background staining due to a small amount of toner being developed in white areas (unexposed areas) that are not supposed to be printed. The developing roller was attached to a process cartridge for a color laser printer (product name: HP Color LaserJet Enterprise M653dn, manufactured by HP), and the process cartridge was attached to the color laser printer, and the amount of fogging was evaluated as follows. For the evaluation, a cyan process cartridge for the color laser printer (product name: HP656X High Yield Cyan Original LaserJet Toner Cartridge, manufactured by HP) was used. The cyan process cartridge was left in a high-temperature and high-humidity environment of 32°C and 95% relative humidity for 16 hours, and then a low-print image with a print rate of 0.2% was continuously output on recording paper in order to perform an evaluation in a very large number of sheets printed under the same environment. However, since toner is consumed by printing, toner was replenished so that the toner weight in the process cartridge became 100 g every time 50,000 sheets were output. After 200,000 sheets were printed, the electrophotographic device was stopped during printing of a solid white image. After development and before transfer, the toner on the photoconductor was temporarily transferred to a transparent tape, and the tape with the toner attached was attached to a recording paper or the like. A tape without toner attached thereto was also attached to the same recording paper at the same time. The optical reflectance was measured from above the tape attached to the recording paper using an optical reflectance measuring device (TC-6DS manufactured by Tokyo Denshoku Co., Ltd.) with a green filter, and the amount of reflectance of the fog was calculated by subtracting it from the reflectance of the tape with no toner attached, and evaluated as the amount of fog. The amount of fog was measured at three or more points on the tape and the average value was calculated. Rank A: The amount of fogging is less than 1.0%. Rank B: The amount of fogging is 1.0% or more and less than 3.0%. Rank C: The amount of fogging is 3.0% or more and less than 5.0%. Rank D: The amount of fogging is 5.0% or more. The evaluation results are shown in Table 8 below.

[0128] [Examples 2 to 19] Using the same method as in Example 1, each resin layer coating material was prepared using the materials shown in Table 5, each impregnation treatment liquid was prepared using the materials shown in Table 6, and each developing roller was manufactured using the combinations shown in Table 7. The resulting developing rollers were evaluated using the same method as in Example 1.

[0129] [Example 20] A developing roller was produced in the same manner as in Example 1, except that the time for immersion in the impregnation treatment liquid was changed to 10 minutes, and evaluation was performed in the same manner as in Example 1.

[0130] [Comparative Examples 1 to 3] Except for not performing the impregnation with the impregnation treatment liquid and the curing treatment, a coating material for the resin layer was prepared using the materials shown in Table 5 in the same manner as in Example 1, a developing roller was produced, and evaluation was performed in the same manner as in Example 1.

[0131] [Comparative Examples 4 to 6] Using the same method as in Example 1, each resin layer coating material was prepared using the materials shown in Table 5, each impregnation treatment liquid was prepared using the materials shown in Table 6, and each developing roller was manufactured using the combinations shown in Table 7. The resulting developing rollers were evaluated using the same method as in Example 1. The evaluation results are shown in Table 8.

[0132] [Table 5]

[0133] *The numbers in the table indicate the amount of each material in parts by mass. *The materials listed in the table are as follows: "PTGL1000": Product name; Polyol manufactured by Hodogaya Chemical Co., Ltd. "PTMG1000": Product name; Polyol manufactured by Mitsubishi Chemical Corporation. "MR-400" ("Millionate MR-400"; product name; isocyanate compound (polymeric MDI) manufactured by Tosoh Corporation. "SUNBLACK X15" (product name: carbon black manufactured by Asahi Carbon Co., Ltd. (volatile content: 2.1%). "#5": (product name; carbon black manufactured by Mitsubishi Chemical Corporation (volatile content: 0.4%)). "#4000": (product name; carbon black manufactured by Mitsubishi Chemical Corporation (volatile content: 0.3%)). "AEROSIL50": Product name; Silica manufactured by Nippon Aerosil Co., Ltd. "50HB-100" (Newpol 50HB-100): Product name; Monool (poly(oxyethyleneoxypropylene) glycol monobutyl ether, molecular weight Mn = 510) manufactured by Sanyo Chemical Industries, Ltd. "MX-150" (Kesnow MX-150): Product name; cross-linked acrylic particles manufactured by Soken Chemical Industries, Ltd. "LCB-19": Product name; Chain acrylic resin manufactured by Mitsubishi Chemical Corporation "UCN-5090": Product name; Cross-linked urethane resin particles manufactured by Dainichiseika Chemicals Co., Ltd., average particle size 9μm

[0134] [Table 6]

[0135] *The numbers in the table indicate the amount of each material in parts by mass. *The materials listed in the table are as follows: EBECRYL145: Product name; Difunctional acrylic monomer manufactured by Daicel Allnex EBECRYL11: Product name; Difunctional acrylic monomer manufactured by Daicel Allnex NK Ester 9G: Product name; Difunctional acrylic monomer manufactured by Shin-Nakamura Chemical Co., Ltd. EBECRYL160S: Product name; Daicel-Allnex trifunctional acrylic monomer HDDA: Product name; Difunctional acrylic monomer manufactured by Daicel Allnex TMPTA: Trade name; Daicel Allnex trifunctional acrylic monomer Ethylene glycol diglycidyl ether: Tokyo Chemical Industry Co., Ltd. Bifunctional glycidyl ether monomer Neopentyl glycol diglycidyl ether: Tokyo Chemical Industry Co., Ltd. Bifunctional glycidyl ether monomer San-Aid SI-110L: Product name; Photopolymerization initiator; PF6 / aromatic sulfonium salt, manufactured by Sanshin Chemical Industry Co., Ltd. IRGACURE184: Product name; Photopolymerization initiator manufactured by BASF

[0136] [Table 7]

[0137] [Table 8]

[0138] [Consideration of evaluation results] All of the electrophotographic members of Examples 1 to 20 have an elastic layer as a surface layer, and contain a first resin and a second resin. The second resin is at least one of a crosslinked acrylic resin having an ether bond (-COC-) and a crosslinked epoxy resin having an ether bond (-COC-). All of them satisfy the condition A1>A2, and it can be confirmed that the crosslinked urethane resin and the crosslinked acrylic resin or crosslinked urethane resin form an IPN structure in the first region from the outer surface of the surface layer to a depth of 0.1 μm. As a result, even in a durability evaluation by printing multiple sheets under a high temperature and high humidity environment, a high-quality electrophotographic image can be obtained without fog. Whereas in Example 20, T1=T2, in Example 14, T1>T2 is satisfied, and a high-quality electrophotographic image with less fog can be obtained. In Example 17, the surface layer is formed using an impregnation treatment liquid containing a trifunctional monomer, whereas in Examples 14 to 16, 18, and 19, the surface layer is formed using an impregnation treatment liquid containing a bifunctional monomer, and the latter are able to obtain high-quality electrophotographic images with less fogging. In Example 13, carbon black with a volatile content of less than 0.4% was used, whereas in Examples 12 and 14, carbon black with a volatile content of 0.4% or more was used, making it possible to obtain high-quality electrophotographic images with less fog. In Examples 5, 6, 8, and 10, non-aromatic ring cations are used as the ionic compounds, whereas in Examples 1 to 4, 7, and 9, nitrogen-containing aromatic ring cations are used. The latter are capable of obtaining high-quality electrophotographic images with less fogging. On the other hand, in Comparative Example 1, the step of impregnating the toner with an acrylic monomer or a glycidyl ether monomer and the step of curing the impregnated acrylic monomer or glycidyl ether monomer were not performed, and as a result, the surface layer did not contain an IPN structure, resulting in a low-quality electrophotographic image with fog. In Comparative Example 2, the surface layer contains crosslinked acrylic particles, but the process of impregnating the outer surface of the surface layer with an acrylic monomer or a glycidyl ether monomer and the process of curing the impregnated acrylic monomer or glycidyl ether monomer are not carried out, so the surface layer does not contain an IPN structure, resulting in a low-quality electrophotographic image with fog. Comparative Example 3 contains a chain acrylic resin but does not contain an IPN structure (A1=A2), resulting in a low-quality electrophotographic image with fog. In Comparative Examples 4 to 6, although an IPN structure (A1>A2) is included, an acrylic monomer having an ether bond is not used, and therefore the molecular mobility of the cations is not sufficiently suppressed, resulting in low-quality electrophotographic images with fog. [Explanation of symbols]

[0139] 1: Surface layer 2: Core body 3: Middle layer 11: Lamp holder with built-in water-cooled heat sink 12: Excimer UV lamp 21: Image carrier 22: Electrostatic member 23: Exposure light 24: Developing materials 25: Toner supply roller 26: Development blade 27: Intermediate transfer belt 28: Primary transfer material 29: Secondary transfer material 30: Cleaning materials 31: Fixing device 32: Recording paper transport route 41:First area 42:Second area 43: Surface layer 44: Conductive substrate

Claims

1. An electrophotographic member having a conductive substrate and a single elastic layer as a surface layer, the elastic layer includes a first resin, a second resin, and an anion; the first resin is a cross-linked urethane resin; The crosslinked urethane resin is a resin having at least one cationic structure selected from the following structural formulas (1) to (6) in the molecule, the second resin is at least one of a crosslinked acrylic resin having an ether bond and a crosslinked epoxy resin having an ether bond; An electrophotographic member, characterized in that the first resin and the second resin form an interpenetrating polymer network structure in a first region extending from an outer surface of the elastic layer to a depth of 0.1 μm: 【Chemistry 1】 [In structural formula (1), R1 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z1 to Z3 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102) or a monovalent hydrocarbon group having 1 to 4 carbon atoms, with the proviso that at least one of Z1 to Z3 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).] 【Chemistry 2】 [In structural formula (2), R2 and R3 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing five-membered heteroaromatic ring together with the nitrogen atom to which they are bonded. Z4 and Z5 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z6 represents a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d1 represents an integer of 0 or 1. However, at least one of Z4 to Z6 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).] 【Chemistry 3】 [In structural formula (3), R4 and R5 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing 6-membered heteroaromatic ring together with the nitrogen atom to which it is bonded. Z7 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z8 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d2 represents an integer of 0 to 2, and when d2 is 2, each Z8 may be the same or different. However, at least one of Z7 and Z8 is any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102). ] 【Chemistry 4】 [In structural formula (4), R6 and R7 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing heteroalicyclic group together with the nitrogen atom to which they are bonded. Z9 to Z11 each independently represent any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z12 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d3 represents an integer of 0 to 2, and when d3 is 2, Z12 may be the same or different. However, at least one of Z9 to Z12 is any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102). 【Chemistry 5】 [In structural formula (5), R8 represents a divalent hydrocarbon group necessary for forming a nitrogen-containing aromatic ring together with the nitrogen atom to which it is bonded. Z13 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z14 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d4 represents an integer of 0 or 1. However, at least one of Z13 and Z14 is any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).] 【Chemistry 6】 [In structural formula (6), R9 represents a divalent hydrocarbon group necessary for forming a nitrogen-containing alicyclic group together with the nitrogen atom to which it is bonded. Z15 and Z16 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z17 represents a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a hydrocarbon group having 1 to 4 carbon atoms. d5 represents an integer of 0 or 1. However, at least one of Z15 to Z17 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).] 【Chemistry 7】 [In structural formulas (Z101) and (Z102), R10 and R11 each independently represent a divalent hydrocarbon group having a straight chain or a branched chain. The symbol "*" represents a bond to the nitrogen atom in structural formula (1) or a bond to a nitrogen atom in a nitrogen-containing heterocycle or a bond to a carbon atom in a nitrogen-containing heterocycle in structural formulas (2) to (6), and the symbol "**" represents a bond to a carbon atom in the polymer chain constituting the resin having a cationic structure.]

2. An electrophotographic member having a conductive substrate and a single elastic layer as a surface layer, an electrophotographic member comprising: the elastic layer comprising a first resin, a second resin, and an anion; the first resin is a crosslinked urethane resin, and the crosslinked urethane resin has in its molecule at least one cationic structure selected from the following structural formulas (1) to (6); the second resin is at least one of a crosslinked acrylic resin having an ether bond and a crosslinked epoxy resin having an ether bond; a first region from the outer surface of the elastic layer to a depth of 0.1 μm comprises the first resin and the second resin; a peak top temperature of a thermal chromatogram derived from the second resin measured from a first sample sampled from the first region is A1 (° C.); and a peak top temperature of a thermal chromatogram derived from the second resin measured from a second sample obtained by decomposing the first resin contained in the first sample is A2 (° C.), where A1 and A2 satisfy the relationship represented by the following relational formula (1): A1>A2 (1) 【Chemistry 8】 [In structural formula (1), R1 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z1 to Z3 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102) or a monovalent hydrocarbon group having 1 to 4 carbon atoms, with the proviso that at least one of Z1 to Z3 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).] 【Chemistry 9】 [In structural formula (2), R2 and R3 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing five-membered heteroaromatic ring together with the nitrogen atom to which they are bonded. Z4 and Z5 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z6 represents a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d1 represents an integer of 0 or 1. However, at least one of Z4 to Z6 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).] 【Chemistry 10】 [In structural formula (3), R4 and R5 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing 6-membered heteroaromatic ring together with the nitrogen atom to which it is bonded. Z7 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z8 represents any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d2 represents an integer of 0 to 2, and when d2 is 2, each Z8 may be the same or different. However, at least one of Z7 and Z8 is any structure selected from the group consisting of structures represented by structural formulae (Z101) and (Z102). ] 【Chemistry 11】 [In structural formula (4), R6 and R7 each represent a divalent hydrocarbon group necessary for forming a nitrogen-containing heteroalicyclic group together with the nitrogen atom to which they are bonded. Z9 to Z11 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z12 represents a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d3 represents an integer of 0 to 2, and when d3 is 2, each Z12 may be the same or different. However, at least one of Z9 to Z12 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102). ] 【Chemistry 12】 [In structural formula (5), R8 represents a divalent hydrocarbon group necessary for forming a nitrogen-containing aromatic ring together with the nitrogen atom to which it is bonded. Z13 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z14 represents any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a monovalent hydrocarbon group having 1 to 4 carbon atoms. d4 represents an integer of 0 or 1. However, at least one of Z13 and Z14 is any structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).] 【Chemistry 13】 [In structural formula (6), R9 represents a divalent hydrocarbon group necessary for forming a nitrogen-containing alicyclic group together with the nitrogen atom to which it is bonded. Z15 and Z16 each independently represent a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), a hydrogen atom, or a monovalent hydrocarbon group having 1 to 4 carbon atoms. Z17 represents a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102), or a hydrocarbon group having 1 to 4 carbon atoms. d5 represents an integer of 0 or 1. However, at least one of Z15 to Z17 is a structure selected from the group consisting of structures represented by structural formulas (Z101) and (Z102).] 【Chemistry 14】 [In structural formulas (Z101) and (Z102), R10 and R11 each independently represent a divalent hydrocarbon group having a straight chain or a branched chain. The symbol "*" represents a bond to the nitrogen atom in structural formula (1) or a bond to a nitrogen atom in a nitrogen-containing heterocycle or a bond to a carbon atom in a nitrogen-containing heterocycle in structural formulas (2) to (6), and the symbol "**" represents a bond to a carbon atom in the polymer chain constituting the resin having a cationic structure.]

3. When a peak top temperature of a thermal chromatogram derived from the first resin in the first region is T1 (°C), and a peak top temperature of a thermal chromatogram derived from the first resin included in a second region having a thickness of 0.1 μm from the back surface of the elastic layer facing the base toward the outer surface is T2 (°C), 3. The electrophotographic member according to claim 1, wherein T1 and T2 satisfy the relationship represented by the following formula (2): T1>T2 (2)

4. 4. The electrophotographic member according to claim 1, wherein the monomer forming the second resin is a bifunctional monomer.

5. 5. The electrophotographic member according to claim 1, wherein the elastic layer contains carbon black having a volatile content of 0.4% or more.

6. 6. The electrophotographic member according to claim 1, wherein the cationic structure contains a nitrogen-containing aromatic ring.

7. 7. An electrophotographic process cartridge configured to be detachably mountable to a main body of an electrophotographic apparatus, comprising the electrophotographic member according to claim 1.

8. 7. An image forming apparatus comprising an image carrier for carrying an electrostatic latent image, a charging device for primarily charging the image carrier, an exposure device for forming an electrostatic latent image on the primarily charged image carrier, a developing member for developing the electrostatic latent image with toner to form a toner image, and a transfer device for transferring the toner image to a transfer material, wherein the developing member is the electrophotographic member according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Conductive member, process cartridge, and electrophotography device

    JP2001099137A

  • Conductive roll

    JP2003202722A

  • Electrically conductive roller, developing device and image formation device

    JP2011053658A

  • Electrophotographic member, process cartridge, and electrophotographic apparatus

    JP2019191581A